23Na Magnetic Resonance Imaging of the Lower Leg of Acute Heart Failure Patients during Diuretic Treatment - Hammon, Matthias; Großmann, Susan; Linz, Peter; Kopp, Christoph; Dahlmann, Anke; Garlichs, Christoph; Janka, Rolf Matthias; Luft, Friedrich C.; Uder, Michael; Titze, Jens; Cavallaro, Alexander Josef (PLoS ONE, 2015)
Na+ can be stored in muscle and skin without commensurate water accumulation. The aim of this study was to assess Na+ and H2O in muscle and skin with MRI in acute heart failure patients before and after diuretic treatment and in a healthy cohort.Nine patients (mean age 78 years; range 58-87) and nine age and gender-matched controls were studied. They underwent 23Na/1H-MRI at the calf with a custom-made knee coil. Patients were studied before and after diuretic therapy. 23Na-MRI gray-scale measurements of Na+-phantoms served to quantify Na+-concentrations. A fat-suppressed inversion recovery sequence was used to quantify H2O content.Plasma Na+-levels did not change during therapy. Mean Na+-concentrations in muscle and skin decreased after furosemide therapy (before therapy: 30.7±6.4 and 43.5±14.5 mmol/L; after therapy: 24.2±6.1 and 32.2±12.0 mmol/L; p?0.05 and p?0.01). Water content measurements did not differ significantly before and after furosemide therapy in muscle (p = 0.17) and only tended to be reduced in skin (p = 0.06). Na+-concentrations in calf muscle and skin of patients before and after diuretic therapy were significantly higher than in healthy subjects (18.3±2.5 and 21.1±2.3 mmol/L).23Na-MRI shows accumulation of Na+ in muscle and skin in patients with acute heart failure. Diuretic treatment can mobilize this Na+-deposition; however, contrary to expectations, water and Na+-mobilization are poorly correlated.
EVALuna2:3828

3 Tesla (23)Na Magnetic Resonance Imaging During Acute Kidney Injury - Hammon, Matthias; Großmann, Susan; Linz, Peter; Seuss, Hannes; Hammon, Rebecca; Rosenhauer, Daniela; Janka, Rolf Matthias; Luft, Friedrich C.; Titze, Jens; Uder, Michael; Dahlmann, Anke; Cavallaro, Alexander Josef (Academic Radiology, 2017)
Sodium and proton magnetic resonance imaging ((23)Na/(1)H-MRI) have shown that muscle and skin can store Na(+) without water. In chronic renal failure and in heart failure, Na(+) mobilization occurs, but is variable depending on age, dialysis vintage, and other features. Na(+) storage depots have not been studied in patients with acute kidney injury (AKI).We studied 7 patients with AKI (mean age: 51.7 years; range: 25-84) and 14 age-matched and gender-matched healthy controls. All underwent (23)Na/(1)H-MRI at the calf. Patients were studied before and after acute hemodialysis therapy within 5-6 days. The (23)Na-MRI produced grayscale images containing Na(+) phantoms, which served to quantify Na(+) contents. A fat-suppressed inversion recovery sequence was used to quantify H2O content.Plasma Na(+) levels did not change. Mean Na(+) contents in muscle and skin did not significantly change following four to five cycles of hemodialysis treatment (before therapy: 32.7 ± 6.9 and 44.2 ± 13.5 mmol/L, respectively; after dialysis: 31.7 ± 10.2 and 42.8 ± 11.8 mmol/L, respectively; P > .05). Water content measurements did not differ significantly before and after hemodialysis in muscle and skin (P > .05). Na(+) contents in calf muscle and skin of patients before hemodialysis were significantly higher than in healthy subjects (16.6 ± 2.1 and 17.9 ± 3.2) and remained significantly elevated after hemodialysis.Na(+) in muscle and skin accumulates in patients with AKI and, in contrast to patients receiving chronic hemodialysis and those with acute heart failure, is not mobilized with hemodialysis within 5-6 days.
EVALuna2:14621

3 Tesla (23)Na magnetic resonance imaging during aerobic and anaerobic exercise - Hammon, Matthias; Großmann, Susan; Linz, Peter; Kopp, Christoph; Dahlmann, Anke; Janka, Rolf Matthias; Uder, Michael; Titze, Jens; Cavallaro, Alexander Josef (Academic Radiology, 2015)
The aim of the work described here was to determine the feasibility of monitoring Na(+) concentration and distribution in muscle/skin during aerobic/anaerobic exercise with (23)Na magnetic resonance imaging (MRI).The Na(+) concentration and water content of muscle/skin of the left lower leg of six healthy subjects (mean age, 26 years; range, 22-30 years; three men and three women) were assessed before and after aerobic/anaerobic cycle ergometry and during recovery with 3-T (23)Na/(1)H MRI. (23)Na MRI was performed with a custom-made knee coil. A gradient echo sequence with an acquisition time of 3.25 minutes, echo time of 2.07 ms, repetition time of 100 ms, and spatial resolution of 3 × 3 × 30 mm(3) was applied. Phantoms with increasing sodium concentration served for quantification via linear extrapolation. Blood values were determined by blood gas analysis.The concentration of Na(+) significantly increased during anaerobic exercise in all muscle compartments except the medial gastrocnemius muscle, whereas no significant change was observed in most muscle compartments during aerobic exercise (only the soleus muscle exhibited a significant increase in Na(+) concentration during aerobic exercise: 1.6 ± 1.5 mmol/kg, 4.5%, P = .046). During anaerobic exercise, the mean Na(+) concentration of the triceps surae and the whole leg increased by 9.0% (3.1 ± 2.1 mmol/kg, P = .016) and 6.5% (2.2 ± 1.3 mmol/kg, P < .01). MRI revealed a water-independent increase in Na(+) concentration in most muscle compartments during anaerobic exercise. Na(+) concentration significantly decreased during recovery after anaerobic and aerobic exercise in all muscle compartments except the soleus. The Na(+) concentration of the skin did not significantly change during anaerobic/aerobic exercise.Sodium(23) MRI allows reliable and noninvasive visualization and quantification of Na(+) concentration and distribution in muscle and skin during exercise. (23)Na MRI can be used to gain new insights into Na(+) homeostasis, presumably leading to better comprehension of pathophysiology.
EVALuna2:3827

Accuracy of MRI-Compatible Contrast Media Injectors - Saake, Marc; Wüst, Wolfgang; Becker, Stefan; Uder, Michael; Janka, Rolf Matthias (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Purpose: To analyze the exactness of MRI-compatible contrast media (CM) injectors in an experimental setup and clinical use. Materials and Methods: Ejected fluid volumes and amounts of CM were quantified for single and double piston injections. The focus was on small volumes, as used in pediatric examination and test-bolus measurements. Samples were collected before and after clinical MRI scans and amounts of CM were measured. Results: For single piston injections the volume differences were minimal (mean difference 0.01 ml). For double piston injections the volume of the first injection was decreased (mean 20.74 ml, target 21.00 ml, p < 0.01). After a position change of the Y-piece of the injection system, the amount of CM differed significantly from the target value (mean 1.23 mmol and 0.83 mmol at 1 ml/s flow rate, target 1.00 mmol, p < 0.01), independently of the wait time. The clinical samples confirmed these findings. Conclusion: The pistons of modern CM injectors work exactly. However, for small CM volumes the injected amount of CM can differ significantly from the target value in both directions. Influence factors are an incomplete elimination of air and exchange processes between the CM and saline chaser in the injection system. Key Points: o?In MRI examinations of children and test-bolus measurements, small amounts of CM are used.o?The accuracy of single piston injections is high.o?In double piston injections the injected amount of CM can differ significantly from the target value. Citation Format: o?Saake M, Wuest W, Becker S et al. Genauigkeit von MRT-kompatiblen Kontrastmittelinjektoren. Fortschr Röntgenstr 2014; 186: 253 - 259.
EVALuna2:14348

Accuracy of MRI-CT registration in brain stereotactic radiotherapy: Impact of MRI acquisition setup and registration method - Masitho, Siti; Putz, Florian; Mengling, Veit; Reißig, Lisa; Voigt, Raphaela; Bäuerle, Tobias; Janka, Rolf Matthias; Fietkau, Rainer; Bert, Christoph (Zeitschrift für Medizinische Physik, 2022)
Background: In MR-based radiotherapy (RT), MRI images are co-registered to the planning CT to leverage MR image information for RT planning. Especially in brain stereotactic RT, where typical CTV-PTV margins are 1-2 mm, high registration accuracy is critical. Several factors influence the registration accuracy, including the acquisition setup during MR simulation and the registration methods. Purpose: In this work, the impact of the MRI acquisition setup and registration method was evaluated in the context of brain RT, both geometrically and dosimetrically. Methods and Materials: MRI of 20 brain radiotherapy patients was acquired in two MRI acquisition setups (RT and diagnostic). Three different automatic registration tools provided by three treatment planning systems were used to rigidly register both MRIs and CT in addition to the clinical registration. Segmentation-based evaluation using Hausdorff Distance (HD)/Dice Similarity Coefficient and landmark-based evaluation were used as evaluation metrics. Dose-volume-histograms were evaluated for target volumes and various organs at risks. Results: MRI acquisition in the RT setup provided a similar head extension as compared to the planning CT. The registration method had a more significant influence than the acquisition setup (Wilcoxon signed-rank test, p<0.05). When registering using a less optimal registration method, the RT setup improved the registration accuracy compared to the diagnostic setup (Difference: ΔMHD = 0.16 mm, ΔHDP95 = 0.64 mm, mean Euclidean distance (ΔmEuD) = 2.65 mm). Different registration methods and acquisition setups lead to the variation of the clinical DVH. Acquiring MRI in the RT setup can improve PTV and GTV coverage compared to the diagnostic setup. Conclusions: Both MRI acquisition setup and registration method influence the MRI-CT registration accuracy in brain RT patients geometrically and dosimetrically. MR-simulation in the RT setup assures optimal registration accuracy if automatic registration is impaired, and therefore recommended for brain RT.
CRIS-Team Scopus Importer:2022-11-11
Keywords: Brain radiotherapy; Intracranial stereotactic radiotherapy; Magnetic-resonance imaging; Patient immobilization; Registration

Acoustic radiation force impulse tissue characterization of the anterior talofibular ligament: a promising noninvasive approach in ankle imaging - Hotfiel, Thilo; Heiß, Rafael; Janka, Rolf Matthias; Forst, Raimund; Raithel, Martin; Lutter, Christoph; Gelse, Kolja; Pachowsky, Milena; Golditz, Tobias (The physician and sportsmedicine, 2018)
OBJECTIVES: The anterior talofibular ligament (ATFL) is the most frequently injured ligament during inversion strains of the ankle. The purpose of this study was to evaluate the feasibility of acoustic radiation force impulse (ARFI) elastography and to determine the in vivo mechanical properties of the ATFL in healthy athletes. METHODS: Sixty healthy athletes (32 female, 28 male; 28.9 ± 2.1 years) were recruited from the medical and sports faculty. ARFI values, represented as shear wave velocities (SWVs) as well as conventional ultrasound were obtained for the ATFL in neutral ankle position. A clinical assessment was performed in which the American Orthopaedic Foot & Ankle Society (AOFAS) Ankle-Hindfoot Score and the functional ankle ability measure (FAAM) were collected. Interobserver and intraobserver reliability (repeated sessions and repeated days) were assessed using an intra class correlation coefficient (ICC) and typical error (TE) calculation in absolute (TE) and relative units as coefficient of the variation (CV). RESULTS: SWV values of the ATFL had an average velocity of 1.79 ± 0.20 m/s for all participants, with an average of 1.72 ± 0.36 m/s for females and 1.85 ± 0.31 m/s for males. The interobserver and intraobserver reliability revealed an ICC of 0.902 and 0.933 (TE of 0.67 (CV: 5.2%) and 0.52 (CV: 3.84%)), respectively. FAAM and AOFAS revealed the best possible scores. CONCLUSION: ARFI seems to be a valuable diagnostic modality and represents a promising imaging marker for the assessment and monitoring of ankle ligaments in the context of acute and chronic ankle instabilities; ARFI could also be used to investigate loading or sport dependent adaptions.
EVALuna2:36110

Advanced Modeled Iterative Reconstruction (ADMIRE) Facilitates Radiation Dose Reduction in Abdominal CT - Ellmann, Stephan; Kammerer, Ferdinand; Allmendinger, Thomas; Hammon, Matthias; Janka, Rolf Matthias; Lell, Michael; Uder, Michael; Kramer, Manuel (Academic Radiology, 2018)
RATIONALE AND OBJECTIVES: This study aimed to determine the potential degree of radiation dose reduction achievable using Advanced Modeled Iterative Reconstruction (ADMIRE) in abdominal computed tomography (CT) while maintaining image quality. Moreover, this study compared differences in image noise reduction of this iterative algorithm with radiation dose reduction. METHODS: Eleven consecutive patients scheduled for abdominal CT were scanned according to our institute's standard protocol (100 kV, 289 reference mAs). Using a proprietary reconstruction software, CT images of these patients were reconstructed as either full-dose weighted filtered back projections or with simulated radiation dose reductions down to 10% of the full-dose level and ADMIRE at either strength 3 or strength 5. Images were marked with arrows pointing on anatomic structures of the abdomen, differing in their contrast to the surrounding tissue. Structures were grouped into high-, medium-, and low-contrast subgroups. In addition, the intrinsic noise of these structures was measured. That followed, image pairs were presented to observers, with five readers assessing image quality using two-alternative-forced-choice comparisons. In total, 3000 comparisons were performed that way. RESULTS: Both ADMIRE 3 and 5 decreased noise of the anatomic structures significantly compared to the filtered back projection, with an additional significant difference between ADMIRE 3 and 5. Radiation dose reduction potential for ADMIRE ranged from 29.0% to 53.5%, with no significant differences between ADMIRE 3 and 5 within the contrast subgroups.The potential levels of radiation dose reduction for ADMIRE 3 differed significantly between high-, medium-, and low-contrast structures, whereas for ADMIRE 5, there was only a significant difference between the high- and the medium-contrast subgroups. CONCLUSION: Although ADMIRE 5 permits significantly higher noise reduction potential than ADMIRE 3, it does not facilitate higher levels of radiation dose reduction. ADMIRE nonetheless holds remarkable potential for radiation dose reduction, which features a certain dependency on the contrast of the structure of interest. Applying ADMIRE with a strength of 3 in abdominal CT may permit radiation dose reduction of about 30%.
EVALuna2:34687

Anti-citrullinated protein antibody positivity correlates with cartilage damage and proteoglycan levels in patients with rheumatoid arthritis in the hand joints - Renner, Nina; Krönke, Gerhard; Rech, Jürgen; Uder, Michael; Janka, Rolf Matthias; Lauer, Lars; Paul, Dominik; Herz, Barbara; Schlechtweg, Philipp; Hennig, Friedrich; Schett, Georg; Welsch, Götz (Arthritis and Rheumatology, 2014)
Objective: To investigate the factors associated with cartilage proteoglycan content in patients with rheumatoid arthritis (RA) Methods: 32 RA patients received high-field 3 Tesla Gadolinium-Enhanced MRI of Cartilage (dGEMRIC) for determining cartilage proteoglycan content. Measurements were performed in three individual cartilage regions (medial, central, lateral) of the metacarpophalangeal joints 2 and 3. dGEMRIC values were then related to disease duration, disease activity, anti-citrullinated protein antibody (ACPA) status, rheumatoid factor status and C-reactive protein level. Results: dGEMRIC values were not significantly different between the MCP2 and MCP3 joint. Inter-class correlations were high (>0.92) for all three (medial, central and lateral) cartilage compartments. dGEMRIC values were significantly lower in RA patients with longer disease duration (>=3 years) and those with ACPA positivity than those with a short disease duration (<3 years)(p=0.034) or negative ACPA (p=0.0002), respectively. In contrast, no association between cartilage proteoglycan content and disease activity, C-reactive protein level and rheumatoid factor status was found. Conclusion: Decreased cartilage proteoglycan content in RA patients is associated with disease duration and ACPA positivity but not with the actual disease activity, CRP level or rheumatoid factor status. These data suggest that the cumulative burden of inflammation as well as ACPA are the determinants for cartilage damage in RA.
EVALuna2:12983

A Retrieval-Based Computer-Aided Diagnosis System for theCharacterization of Liver Lesions in CT Scans - Dankerl, Peter; Cavallaro, Alexander Josef; Tsymbal, Alexey; Costa, Maria Jimena; Suehling, Michael; Janka, Rolf Matthias; Uder, Michael; Hammon, Matthias (Academic Radiology, 2013)
Rationale and Objectives: To evaluate a computer-aided diagnosis (CADx) system for the characterization of liver lesions in computed tomography (CT) scans. The stand-alone predictive performance of the CADx system was assessed and compared to that of three radiologists who were provided with the same amount of image information to which the CADx system had access. Materials and Methods: The CADx system operates as an image search engine exploiting texture analysis of liver lesion image data forthe lesion in question and lesions from a database. A region of interest drawn around an indeterminate liver lesion is used as input query. The CADx system retrieves lesions of similar histology (benign/malignant), density (hypodense/hyperdense), or type (cyst/hemangioma/metastasis). The system's performance was evaluated with leave-one-patient-out receiver operating characteristic area under the curve on 685 CT scans from 372 patients that contained 2325 liver lesions (193<1cm3). Sensitivity, specificity, and positive and negative predictive values were evaluated separately for subcentimeter lesions. Results were compared to those of three radiologists who rated 83 liver lesions (20 hemangiomas, 20 metastases, 20 cysts, 20 hepatocellular carcinomas, and 3 focal nodular hyperplasias) displaying only the liver. Results: The CADx system's leave-one-patient-out receiver operating characteristic area under the curve was 97.1% for density, 91.4% for histology, and 95.5% for lesion type. For subcentimeter lesions, input of additional semantic information improved the system's performance. The CADx system has been proved to significantly outperform radiologists in discriminating lesion histology and type, provided the radiologists have no access to information other than the image. The radiologists were most reliable in diagnosing hemangioma given the limited image data. Conclusions: The CADx system under study discriminated reliably between various liver lesions, even outperforming radiologists whenaccessing the same image information and demonstrated promising performance in classifying subcentimeter lesions in particular. © 2013 AUR.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Computer-assisted diagnosis; Hepatobiliary; Imaging technology; Special interest

Artificial intelligence (AI) in diagnostic imaging. - Braunschweig, Rainer; Kildal, Daniela; Janka, Rolf Matthias (Röfo: Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2024)
PURPOSE: In the last few years artificial intelligence (AI) has increasingly become a topic of interest, especially in diagnostic imaging. There are two main expected potential benefits: workflow effectiveness and diagnostic support systems, particularly as far as quality assurance is concerned. METHODS: To meet these objectives, it is necessary to define what artificial intelligence in medicine means and to discuss which detailed steps should be fulfilled, e. g., for MSK imaging in the daily routine. In addition, this article provides an overview of what is necessary for an efficient IT-based workflow including the clinical question, the choice of modalities and investigation protocols, structured reports, and clinical classification. This is particularly interesting for potential providers, who are keen to apply new soft skills to support imaging diagnostic processes. RESULTS: The use of AI-supported diagnostic imaging could result in a paradigm shift from a modality-oriented to a clinical problem-oriented workflow. In order to streamline trauma, degeneration, inflammation, and oncology-MSK diagnostic imaging, the potential benefits of AI-based workflow optimization should be taken advantage of. The following article describes a five-point plan combining patient expectations and specialized radiological standards with respect to investigation protocols and reports. Moreover, this AI-based strategy could help to improve interdisciplinary networking, e. g., boards etc., and facilitate the required leap in quality towards "personalized precision medicine" for the patient. According to the global discussion, there is a need to point out that it is not currently realistic to replace doctors with AI. KEY POINTS: · AI as support-system has a paramount clinical impact. · AI in the daily routine could be for work-flow-support (processing) - a physician-replacement is un-realistic yet. · Standardization of work-flow by AI could be an important contribution of quality assurance. CITATION FORMAT: · Braunschweig R, Kildal D, Janka R. Artificial intelligence (AI) in diagnostic imaging . Fortschr Röntgenstr 2024; DOI: 10.1055/a-2208-6487.
EVALuna2:568213

Assessment of sorafenib induced changes in tumor perfusion of uveal melanoma metastases with dynamic contrast-enhanced ultrasound (DCE-US) - Wildner, Dane; Heinzerling, Lucie; Scheulen, Max E.; Kämpgen, Eckhart; Schuler, Gerold; Strobel, Deike; Janka, Rolf Matthias; Neurath, Markus; Sturm, Jörg; Knieling, Ferdinand (Journal of Cancer Research and Clinical Oncology, 2021)
Purpose Dynamic contrast-enhanced ultrasound (DCE-US) was used to monitor early response to sorafenib therapy in patients with liver metastases from uveal melanoma. Methods In total, 21 patients with liver metastases were recruited within a prospective trial and underwent daily sorafenib therapy. DCE-US of a target lesion was performed before initiation of treatment, on day 15 and 56. Two independent blinded investigators performed software analysis for DCE-US parameters and inter-observer-correlation was calculated. Response to treatment was evaluated on day 56. DCE-US parameters were correlated with clinical response and RECIST1.1 criteria. Results Inter-observer-correlation (r) of DCE-US parameters [time-to-peak (TTP), mean-transit-time (MTT), peak intensity (PI), regional blood volume (RBV), regional blood flow (RBF)] at baseline, day 15, and day 56 was highly significant (r-range 0.73-0.97, all p < 0.001). Out of 17 evaluable patients, 12 patients survived day 56 (clinical responders, cRE), whereas, five patients died before day 56 and were classified as non-responders (cNR). TTP values significantly increased in the cRE group 15 days after initiation of treatment for investigator 1 (p = 0.034) and at day 56 for both investigators (p = 0.028/0.028). MTT had increased significantly in the cRE group on day 56 (p = 0.037/0.022). In the cNR group changes for TTP and MTT remained insignificant. Thus, increase of the DCE-US parameters TTP and MTT are associated with response to treatment and prognosis. Conclusion An increase of TTP and MTT at frequent intervals could serve as a surrogate marker for early response evaluation to anti-angiogenic treatment of metastatic uveal melanoma.
CRIS-Team WoS Importer:2021-06-04

Automated Heart Localization in Cardiac Cine MR Data - Hoffmann, Roxana; Kranz, Franziska; Siegl, Christian; Janka, Rolf Matthias; Grosso, Roberto; Greiner, Günther (Bildverarbeitung für die Medizin 2016, 2016)
Cardiac MRI is the modality of choice in cardiology for the assessment of the ventricular function, since the heart’s anatomy is visualized with high resolution. This functional assessment is a timeconsuming task for the cardiac radiologist when performed manually. Therefore, computer-driven diagnostic solutions are of particular importance for clinical applications. In order to ensure the success of such computer aided diagnosis algorithms however, a correct, initial localization of the heart region in the raw data is crucial. For this purpose, we present a novel, simple and fully automated approach for localizing the heart region in cardiac cine MR data. Without the need for prior knowledge or training datasets, this method enables a ready to use application for a robust localization. This processing step is a fundamental component for the development of integrated automated applications.

Begleitwort zum Curriculum für die Facharztausbildung und die Weiterbildung in der Muskuloskelettalen Radiologie - Braunschweig, Rainer; Janka, Rolf Matthias; Regier, Marc (Radiologe, 2020)
CRIS-Team Scopus Importer:2020-04-28

Biomechanical knee cartilage analysis in young professional soccer players by a T2 mapping unloading algorithm - Welsch, Götz; Waldenmeier, L; Evers, C; Janka, Rolf Matthias; Uder, Michael; Hennig, Friedrich; Lochmann, Matthias (Osteoarthritis and Cartilage, 2014)

Blood Pressure Pattern and Target Organ Damage in Patients With Chronic Kidney Disease - Scheppach, Johannes B.; Raff, Ulrike; Toncar, Sebastian; Ritter, Christian; Klink, Thorsten; Stoerk, Stefan; Wanner, Christoph; Schlieper, Georg; Saritas, Turgay; Reinartz, Sebastian D.; Floege, Juergen; Janka, Rolf Matthias; et al. (Hypertension, 2018)
In patients with chronic kidney disease, data on blood pressure (BP) pattern and its association with target organ damage, which indicates elevated cardiovascular risk, are sparse. In 305 treated hypertensive chronic kidney disease patients, we assessed BP pattern, left ventricular mass (magnetic resonance imaging), intima-media thickness (ultrasound), 24-hour-pulse wave velocity and 24-hour-central augmentation index (Mobil-O-Graph). Controlled hypertension (normal office and ambulatory BP) was found in 41% and sustained uncontrolled hypertension (elevated office and ambulatory BP) in 30% of patients. Misclassification of BP status occurred in 29%: white coat uncontrolled hypertension (elevated office but normal ambulatory BP) was detected in 11% and masked uncontrolled hypertension (normal office but elevated ambulatory BP) in 18% of patients. Left ventricular mass was increased in white coat uncontrolled hypertension (+11.2 g), masked uncontrolled hypertension (+9.4 g), and sustained uncontrolled hypertension (+16.6 g) compared with controlled hypertension. Intima-media thickness was similar across all 4 BP groups. Twenty-four hour-pulse wave velocity and 24-hour-central augmentation index were increased in masked uncontrolled hypertension (+0.5 m/sec and +2.5%) and sustained uncontrolled hypertension (+0.5 m/sec and +2.9%) compared with controlled hypertension. In conclusion, based on office BP measurements, misclassification of true BP status occurred in almost one-third of chronic kidney disease patients. Both types of misclassification (white coat uncontrolled hypertension and masked uncontrolled hypertension) were associated with parameters of target organ damage. Ambulatory BP monitoring should be used routinely to identify chronic kidney disease patients at high cardiovascular risk.
EVALuna2:34688

Breast MRI at Very Short TE (minTE): Image Analysis of minTE Sequences on Non-Fat-Saturated, Subtracted T1-Weighted Images - Wenkel, Evelyn; Janka, Rolf Matthias; Geppert, Christian; Kämmerer, Nadine; Hartmann, Arndt; Uder, Michael; Hammon, Matthias; Brand, Michael (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2017)
Purpose The aim was to evaluate a minimum echo time (minTE) protocol for breast magnetic resonance imaging (MRI) in patients with breast lesions compared to a standard TE (nTE) time protocol. Methods Breasts of 144 women were examined with a 1.5 Tesla MRI scanner. Additionally to the standard gradient-echo sequence with nTE (4.8 ms), a variant with minimum TE (1.2 ms) was used in an interleaved fashion which leads to a better temporal resolution and should reduce the scan time by approximately 50 %. Lesion sizes were measured and the signal-to-noise ratio (SNR) as well as the contrast-to-noise ratio (CNR) were calculated. Subjective confidence was evaluated using a 3-point scale before looking at the nTE sequences (1 = very sure that I can identify a lesion and classify it, 2 = quite sure that I can identify a lesion and classify it, 3 = definitely want to see nTE for final assessment) and the subjective image quality of all examinations was evaluated using a four-grade scale (1 = sharp, 2 = slight blur, 3 = moderate blur and 4 = severe blur/not evaluable) for lesion and skin sharpness. Lesion morphology and contrast enhancement were also evaluated. Results With minTE sequences, no lesion was rated with "definitely want to see nTE sequences for final assessment". The difference of the longitudinal and transverse diameter did not differ significantly (p > 0.05). With minTE, lesions and skin were rated to be significantly more blurry (p < 0.01 for lesions and p < 0.05 for skin). There was no difference between both sequences with respect to SNR, CNR, lesion morphology, contrast enhancement and detection of multifocal disease. Conclusion Dynamic breast MRI with a minTE protocol is feasible without a major loss of information (SNR, CNR, lesion morphology, contrast enhancement and lesion sizes) and the temporal resolution can be increased by a factor of 2 using minTE sequences. Key points · Increase of temporal resolution for a better in-flow curve.. · Dynamic breast MRI with a shorter TE time is possible without relevant loss of information.. · Possible decrease of the overall scan time.. Citation Format · Wenkel E, Janka R, Geppert C et al. Breast MRI at Very Short TE (minTE): Image Analysis of minTE Sequences on Non-Fat-Saturated, Subtracted T1-Weighted Images. Fortschr Röntgenstr 2017; 189: 137 - 145.
EVALuna2:6843

Cardiac MRI: An Alternative Method to Determine the Left Ventricular Function - Michler, Kerstin; Hessman, Christopher; Prümmer, Marcus; Achenbach, Stephan; Uder, Michael; Janka, Rolf Matthias (Diagnostics, 2023)
(1) Background: With the conventional contour surface method (KfM) for the evaluation of cardiac function parameters, the papillary muscle is considered to be part of the left ventricular volume. This systematic error can be avoided with a relatively easy-to-implement pixel-based evaluation method (PbM). The objective of this thesis is to compare the KfM and the PbM with regard to their difference due to papillary muscle volume exclusion. (2) Material and Methods: In the retrospective study, 191 cardiac-MR image data sets (126 male, 65 female; median age 51 years; age distribution 20–75 years) were analysed. The left ventricular function parameters: end-systolic volume (ESV), end-diastolic volume (EDV), ejection fraction (EF) and stroke volume (SV) were determined using classical KfW (syngo.via and cvi42 = gold standard) and PbM. Papillary muscle volume was calculated and segmented automatically via cvi42. The time required for evaluation with the PbM was collected. (3) Results: The size of EDV was 177 mL (69–444.5 mL) [average, [minimum–maximum]], ESV was 87 mL (20–361.4 mL), SV was 88 mL and EF was 50% (13–80%) in the pixel-based evaluation. The corresponding values with cvi42 were EDV 193 mL (89–476 mL), ESV 101 mL (34–411 mL), SV 90 mL and EF 45% (12–73%) and syngo.via: EDV 188 mL (74–447 mL), ESV 99 mL (29–358 mL), SV 89 mL (27–176 mL) and EF 47% (13–84%). The comparison between the PbM and KfM showed a negative difference for end-diastolic volume, a negative difference for end-systolic volume and a positive difference for ejection fraction. No difference was seen in stroke volume. The mean papillary muscle volume was calculated to be 14.2 mL. The evaluation with PbM took an average of 2:02 min. (4) Conclusion: PbM is easy and fast to perform for the determination of left ventricular cardiac function. It provides comparable results to the established disc/contour area method in terms of stroke volume and measures “true” left ventricular cardiac function while omitting the papillary muscles. This results in an average 6% higher ejection fraction, which can have a significant influence on therapy decisions.
CRIS-Team Scopus Importer:2023-05-05
Keywords: cardiac MRI; cine MRI; ejection fraction; left ventricular function; MRI

Cardiac MRI in Children and Adolescents Who Have Undergone Surgical Repair of Right-Sided Congenital Heart Disease: Automated Left Ventricular Volumes and Function Analysis and Effects of Different Manual Adjustments - Rompel, O.; Janka, Rolf Matthias; May, Matthias; Glöckler, Martin; Cesnjevar, Robert; Dittrich, Sven; Lell, Michael; Uder, Michael; Hammon, Matthias (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2015)
Purpose: To evaluate automated segmentation and the effects of different manual adjustments regarding left ventricular parameter quantification in cardiac magnetic resonance (MR) data on children and adolescents who have undergone surgical repair of right-sided congenital heart disease (CHD). Materials and Methods: Dedicated software (syngo.via, Siemens AG) was used to automatically segment and/or manually adjust the end-diastolic volume (EDV), end-systolic volume (ESV), stroke volume (SV), myocardial mass (MM) and ejection fraction (EF) before/after manual apex/base adjustment (ADJ-step 1) and after manual apex/base/myocardial contour adjustment (ADJ-step 2; reference standard). MR data of 40 patients (13.1 ± 3.1y, 4 - 17y) with repaired CHD with decreased pulmonary blood flow (CHD-DPBF) were evaluated. Intra- and inter-rater reliability was determined for 10 randomly selected patients. Results: The software correctly detected the left ventricle in 38/40 (95 %) patients. EDV after automated segmentation: 119.1 ± 44.0ml; after ADJ-step 1: 115.8 ± 39.5ml; after ADJ-step 2: 116.2 ± 39.4 ml. The corresponding results for ESV were 52.0 ± 18.5/49.6 ± 16.9/49.7 ± 16.4ml; for SV 67.1 ± 28.5/66.2 ± 25.4/66.5 ± 25.5ml; for EF 55.5 ± 7.3/56.7 ± 6.6/56.7 ± 6.3 %; for MM 83.7 ± 35.9/76.2 ± 28.3/74.6 ± 27.2 g. Significant differences were found for ESV/MM/EF comparing the automated segmentation results with these after ADJ-step 1 and ADJ-step 2. No significant differences were found when comparing all results of ADJ-step 1 and ADJ-step 2 or when comparing EDV/SV results. Intra- and inter-rater reliability was excellent. The mean time effort was 63.4 ± 6.9 s for the automated segmentation, 74.2 ± 8.9 s for ADJ-step 1 and 269.5 ± 39.4 s for ADJ-step 2. Conclusion: Automated left ventricular volumes and function analysis in children and adolescents with surgically treated CHD proved to be feasible with excellent intra- and inter-rater reliability. Automated segmentation with manual apex/base adjustment provided clinically acceptable results. Key Points: o?Automated left ventricular volume and function analysis in children and adolescents with surgically treated right-sided heart disease is feasible with excellent intra- and inter-rater reliability.o?Automated segmentation with manual apex/base adjustment provides clinically acceptable results.o?Additional manual myocardial contour adjustment does not significantly improve the results. Citation Format: o?Rompel O, Janka R, May MS et al. Cardiac MRI in Children and Adolescents Who Have Undergone Surgical Repair of Right-Sided Congenital Heart Disease: Automated Left Ventricular Volumes and Function Analysis and Effects of Different Manual Adjustments. Fortschr Röntgenstr 2015; 187: 1099 - 1107.
EVALuna2:14516

Changes in T2 Relaxation Time Mapping of Intervertebral Discs Adjacent to Vertebrae after Kyphoplasty Correlate with the Physical Clinical Outcome of Patients - Wegener, Lisa; Werner, Felix; Kleyer, Arnd; Simon, David; Uder, Michael; Janka, Rolf Matthias; Trattnig, Siegfried; Welsch, Goetz H.; Pachowsky, Milena (Diagnostics, 2022)
(1) Background: To assess whether clinical outcomes correlate with tissue changes in the intervertebral discs (IVDs) after kyphoplasty as treatment for vertebral fractures, quantitative MRI was applied. (2) Methods: Quantitative T2 mapping acquired in a 3 T MRI scanner of the thoracolumbar spine was performed in 20 patients two years after kyphoplasty. The IVDs adjacent and nonadjacent to the treated vertebrae were divided into six regions of interest (ROI), which were further categorised into inner (ROI 2–5) and outer (ROI 1 and 6) parts of the IVDs, and the T2 values were analysed. T2 values of adjacent discs were correlated with the items of questionnaires evaluating the clinical outcome (i.e., 36-Item Short Form Survey). (3) Results: Lower T2 values in adjacent IVDs correlated with poorer physical outcome two years after kyphoplasty. The inner part of the IVDs adjacent to treated vertebrae showed statistically significant lower T2 values in segments L2/L3 and L3/L4 compared to nonadjacent ones. Patients with lower T2 values showed more pain and physical limitations in everyday life. (4) Conclusions: Quantitative T2 mapping can detect IVD degeneration in patients after kyphoplasty and correlates with the physical outcome. This technique could help to gain better insights into alterations in tissue composition following kyphoplasty and the consequences for the patients’ quality of life.
CRIS-Team Scopus Importer:2022-03-11
Keywords: Clinical outcome; Intervertebral disc; Kyphoplasty; MRI; T2 mapping

Chronic popliteal entrapment with calcified lesions results in an acute occlusion after blunt knee trauma in a 17-year-old soccer player - Regus, Susanne; Söder, Stephan; Janka, Rolf Matthias; Lang, Werner (Journal of Vascular Surgery, 2015)
EVALuna2:6687

Combination of an ultrafast TWIST-VIBE Dixon sequence protocol and diffusion-weighted imaging into an accurate easily applicable classification tool for masses in breast MRI - Peter, Sandra C.; Wenkel, Evelyn; Weiland, Elisabeth; Dietzel, Matthias; Janka, Rolf Matthias; Hartmann, Arndt; Emons, Julius; Uder, Michael; Ellmann, Stephan (European Radiology, 2020)
Objectives: This study aimed to develop a tool for the classification of masses in breast MRI, based on ultrafast TWIST-VIBE Dixon (TVD) dynamic sequences combined with DWI. TVD sequences allow to abbreviate breast MRI protocols, but provide kinetic information only on the contrast wash-in, and because of the lack of the wash-out kinetics, their diagnostic value might be hampered. A special focus of this study was thus to maintain high diagnostic accuracy in lesion classification. Materials and methods: Sixty-one patients who received breast MRI between 02/2014 and 04/2015 were included, with 83 reported lesions (60 malignant). Our institute’s standard breast MRI protocol was complemented by an ultrafast TVD sequence. ADC and peak enhancement of the TVD sequences were integrated into a generalised linear model (GLM) for malignancy prediction. For comparison, a second GLM was calculated using ADC and conventional DCE curve type. The resulting GLMs were evaluated for standard diagnostic parameters. For easy application of the GLMs, nomograms were created. Results: The GLM based on peak enhancement of the TVD and ADC was as equally accurate as the GLM based on conventional DCE and ADC, with no significant differences (sensitivity, 93.3%/93.3%; specificity, 91.3%/87.0%; PPV, 96.6%/94.9%; NPV, 84.0%/83.3%; all, p ≥ 0.315). Conclusions: This study presents a method to integrate ultrafast TVD sequences into a breast MRI protocol, allowing a reduction of the examination time while maintaining diagnostic accuracy. A GLM based on the combination of TVD-derived peak enhancement and ADC provides high diagnostic accuracy, and can be easily applied using a nomogram. Key Points: • Ultrafast TWIST-VIBE Dixon sequence protocols in combination with diffusion-weighted imaging allow to shorten breast MRI examinations, while diagnostic accuracy is maintained. • Integrating peak enhancement from the TWIST-VIBE Dixon sequence and the apparent diffusion coefficient into a generalised linear model provides a comprehensible image evaluation approach. • This approach is further facilitated by nomograms.
CRIS-Team Scopus Importer:2020-02-11
Keywords: Breast cancer; Diagnostic imaging; Diffusion magnetic resonance imaging; Magnetic resonance imaging; Statistical model

Comparison of 3T and 7T magnetic resonance imaging for direct visualization of finger flexor pulley rupture: an ex-vivo study. - Bayer, Thomas; Bächter, Lilly; Lutter, Christoph; Janka, Rolf Matthias; Uder, Michael; Schöffel, Völker; Roemer, Frank; Nagel, Armin Michael; Heiß, Rafael (Skeletal Radiology, 2024)
OBJECTIVE: To compare image quality and diagnostic performance of 3T and 7T magnetic resonance imaging (MRI) for direct depiction of finger flexor pulleys A2, A3 and A4 before and after artificial pulley rupture in an ex-vivo model using anatomic preparation as reference. MATERIALS AND METHODS: 30 fingers from 10 human cadavers were examined at 3T and 7T before and after being subjected to iatrogenic pulley rupture. MRI protocols were comparable in duration, both lasting less than 22 min. Two experienced radiologists evaluated the MRIs. Image quality was graded according to a 4-point Likert scale. Anatomic preparation was used as gold standard. RESULTS: In comparison, 7T versus 3T had a sensitivity and specificity for the detection of A2, A3 and A4 pulley lesions with 100% vs. 95%, respectively 98% vs. 100%. In the assessment of A3 pulley lesions sensitivity of 7T was superior to 3T MRI (100% vs. 83%), whereas specificity was lower (95% vs. 100%). Image quality assessed before and after iatrogenic rupture was comparable with 2.74 for 7T and 2.61 for 3T. Visualization of the A3 finger flexor pulley before rupture creation was significantly better for 7 T (p < 0.001). Interobserver variability showed substantial agreement at 3T (κ = 0.80) and almost perfect agreement at 7T (κ = 0.90). CONCLUSION: MRI at 3T allows a comparable diagnostic performance to 7T for direct visualization and characterization of finger flexor pulleys before and after rupture, with superiority of 7T MRI in the visualization of the normal A3 pulley.
EVALuna2:568183

Comparison of Diagnostic Performance and Image Quality between Topup-Corrected and Standard Readout-Segmented Echo-Planar Diffusion-Weighted Imaging for Cholesteatoma Diagnostics - Wiesmüller, Marco; Wüst, Wolfgang; Mennecke, Angelika; May, Matthias; Heiß, Rafael; Führes, Tobit; Janka, Rolf Matthias; Uder, Michael; Dörfler, Arnd; Laun, Frederik Bernd (Diagnostics, 2023)
This study compares the diagnostic performance and image quality of single-shot turbo spin-echo DWI (tseDWI), standard readout-segmented DWI (rsDWI), and a modified rsDWI version (topupDWI) for cholesteatoma diagnostics. Thirty-four patients with newly suspected unilateral cholesteatoma were examined on a 1.5 Tesla MRI scanner. Diagnostic performance was evaluated by calculating and comparing the sensitivity and specificity using histopathological results as the standard of reference. Image quality was independently reviewed by two readers using a 5-point Likert scale evaluating image distortions, susceptibility artifacts, image resolution, lesion conspicuity, and diagnostic confidence. Twenty-five cholesteatomas were histologically confirmed after surgery and originated in the study group. TseDWI showed the highest sensitivity with 96% (95% confidence interval (CI): 88–100%), followed by topupDWI with 92% (95% CI: 81–100%) for both readers. The sensitivity for rsDWI was 76% (95% CI: 59–93%) for reader 1 and 84% (95% CI: 70–98%) for reader 2, respectively. Both tseDWI and topupDWI revealed a specificity of 100% (95% CI: 66–100%) and rsDWI of 89% (95% CI: 52–100%). Both tseDWI and topupDWI showed fewer image distortions and susceptibility artifacts compared to rsDWI. Image resolution was consistently rated best for topupDWI, followed by rsDWI, which both outperformed tseDWI. TopupDWI and tseDWI showed comparable results for lesions’ conspicuity and diagnostic confidence, both outperforming rsDWI. Modified readout-segmented DWI using the topup-correction method is preferable to standard rsDWI and may be regarded as an accurate alternative to single-shot turbo spin-echo DWI in cholesteatoma diagnostics.
CRIS-Team Scopus Importer:2023-04-28
Keywords: cholesteatoma; diffusion-weighted imaging; DWI; echo-planar imaging; EPI; readout-segmented; reduced susceptibility-induced distortions; topup correction; TSE; turbo spin-echo

Comparison of Readout-Segmented Echo-Planar Imaging and Single-Shot TSE DWI for Cholesteatoma Diagnostics - Wiesmüller, Marco; Wüst, Wolfgang; May, Matthias; Ellmann, Stephan; Heiß, Rafael; Saake, Marc; Janka, Rolf Matthias; Uder, Michael; Laun, Frederik Bernd (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: The high diagnostic value of DWI for cholesteatoma diagnostics is undisputed. This study compares the diagnostic value of readout-segmented echo-planar DWI and single-shot TSE DWI for cholesteatoma diagnostics.
CRIS-Team WoS Importer:2021-06-04

Computational hydrodynamics of a typical 3-fin surfboard setup - Falk, Sebastian; Kniesburges, Stefan; Janka, Rolf Matthias; Grosso, Roberto; Becker, Stefan; Semmler, Marion; Döllinger, Michael (Journal of Fluids and Structures, 2019)
Surfing is becoming increasingly popular, and the economic market for surfing products is growing. The performance of the surfboards and the fins has evolved continuously through the experience and innovative spirit of surfers and shapers. However, provided performance characteristics are only subjective and of descriptive nature. Therefore, we apply and analyze objective performance indicators as (1) lift and drag coefficient for each fin and the entire configuration and (2) lift-to-drag ratio for the entire fin configuration. This numerical study investigated a commercial 3-fin configuration, mounted into a rectangular simulation region, considering the flow at several different angles of attack between 0°and 45°. RANS and URANS simulations were performed with the SST k−ω turbulence model at an inflow velocity of 5 m/s. Simulation results showed that the fins have an optimal range of attack angles where they produce the most lift. The lift forces generate a turning moment which forces the board to be turned in direction to the shore favoring the controllability and stability of the surfboard. The higher the angle of attack, the higher is the drag coefficient. Lift-to-drag ratio values showed that for speeding up small attack angles with low drag forces are preferable. Furthermore, unsteady effects as flow separation combined with vortex shedding occur at high angles of attack above 20°which can only be resolved by URANS simulations. These unsteady effects have high negative influences on stability due to high fluctuation amplitudes for lift and drag forces. In summary, this study presents, to the best of the authors’ knowledge, for the first time, steady and unsteady forces on surfboard fins and discusses their potential influences on the surfer's controllability and stability of the surfboard during typical surfing maneuvers.
CRIS-Team Scopus Importer:2019-08-02
Keywords: Computational fluid dynamics (CFD); Fins; Hydrodynamics; STAR-CCM+; Surfboard; Surfing

Computer-aided assessment of anomalies in the scoliotic spine in 3-D MRI images - Jäger, Florian; Hornegger, Joachim; Schwab, Siegfried; Janka, Rolf Matthias (Springer-verlag, 2009)
The assessment of anomalies in the scoliotic spine using Magnetic Resonance Imaging (MRI) is an essential task during the planning phase of a patient's treatment and operations. Due to the pathologic bending of the spine, this is an extremely time consuming process as an orthogonal view onto every vertebra is required. In this article we present a system for computer-aided assessment (CAA) of anomalies in 3-D MRI images of the spine relying on curved planar reformations (CPR). We introduce all necessary steps, from the pre-processing of the data to the visualization component. As the core part of the framework is based on a segmentation of the spinal cord we focus on this. The proposed segmentation method is an iterative process. In every iteration the segmentation is updated by an energy based scheme derived from Markov random field (MRF) theory. We evaluate the segmentation results on public available clinical relevant 3-D MRI data sets of scoliosis patients. In order to assess the quality of the segmentation we use the angle between automatically computed planes through the vertebra and planes estimated by medical experts. This results in a mean angle difference of less than six degrees. © 2009 Springer-Verlag.

Computer-Aided Assessment of Anomalies in the Scoliotic Spine in 3-D MRI Images - Jäger, Florian; Hornegger, Joachim; Schwab, Siegfried; Janka, Rolf Matthias (Medical Image Computing and Computer-Assisted Intervention - MICCAI 2009, 12th International Conference, London, UK, September 20-24, 2009, Proceedings, Part II, 2009)
The assessment of anomalies in the scoliotic spine using Magnetic Resonance Imaging (MRI) is an essential task during the planning phase of a patient's treatment and operations. Due to the pathologic bending of the spine, this is an extremely time consuming process as an orthogonal view onto every vertebra is required. In this article we present a system for computer-aided assessment (CAA) of anomalies in 3-D MRI images of the spine relying on curved planar reformations (CPR). We introduce all necessary steps, from the pre-processing of the data to the visualization component. As the core part of the framework is based on a segmentation of the spinal cord we focus on this. The proposed segmentation method is an iterative process. In every iteration the segmentation is updated by an energy based scheme derived from Markov random field (MRF) theory. We evaluate the segmentation results on public available clinical relevant 3-D MRI data sets of scoliosis patients. In order to assess the quality of the segmentation we use the angle between automatically computed planes through the vertebra and planes estimated by medical experts. This results in a mean angle difference of less than six degrees.
UnivIS-Import:2015-04-16:Pub.2009.tech.IMMD.IMMD5.comput_4

Computer-aided diagnosis in multiparametric mri of the prostate: An open-access online tool for lesion classification with high accuracy - Ellmann, Stephan; Schlicht, Michael; Dietzel, Matthias; Janka, Rolf Matthias; Hammon, Matthias; Saake, Marc; Ganslandt, Thomas; Hartmann, Arndt; Kunath, Frank; Wullich, Bernd; Uder, Michael; Bäuerle, Tobias (Cancers, 2020)
Computer-aided diagnosis (CADx) approaches could help to objectify reporting on prostate mpMRI, but their use in many cases is hampered due to common-built algorithms that are not publicly available. The aim of this study was to develop an open-access CADx algorithm with high accuracy for classification of suspicious lesions in mpMRI of the prostate. This retrospective study was approved by the local ethics commission, with waiver of informed consent. A total of 124 patients with 195 reported lesions were included. All patients received mpMRI of the prostate between 2014 and 2017, and transrectal ultrasound (TRUS)-guided and targeted biopsy within a time period of 30 days. Histopathology of the biopsy cores served as a standard of reference. Acquired imaging parameters included the size of the lesion, signal intensity (T2w images), diffusion restriction, prostate volume, and several dynamic parameters along with the clinical parameters patient age and serum PSA level. Inter-reader agreement of the imaging parameters was assessed by calculating intraclass correlation coefficients. The dataset was stratified into a train set and test set (156 and 39 lesions in 100 and 24 patients, respectively). Using the above parameters, a CADx based on an Extreme Gradient Boosting algorithm was developed on the train set, and tested on the test set. Performance optimization was focused on maximizing the area under the Receiver Operating Characteristic curve (ROCAUC). The algorithm was made publicly available on the internet. The CADx reached an ROCAUC of 0.908 during training, and 0.913 during testing (p = 0.93). Additionally, established rule-in and rule-out criteria allowed classifying 35.8% of the malignant and 49.4% of the benign lesions with error rates of <2%. All imaging parameters featured excellent inter-reader agreement. This study presents an open-access CADx for classification of suspicious lesions in mpMRI of the prostate with high accuracy. Applying the provided rule-in and rule-out criteria might facilitate to further stratify the management of patients at risk.
CRIS-Team Scopus Importer:2020-09-18
Keywords: Artificial intelligence; Computer-aided diagnosis; Machine learning; Prostate cancer; Prostate mpMRI

Curriculum für die Facharztausbildung und die Weiterbildung in der Muskuloskelettalen Radiologie - Braunschweig, Rainer; Janka, Rolf Matthias; Regier, Marc (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2020)
CRIS-Team Scopus Importer:2020-05-19

Detection of Changes in Renal Blood Flow Using Arterial Spin Labeling MRI - Kannenkeril, Dennis; Janka, Rolf Matthias; Bosch, Agnes; Jung, Susanne; Kolwelter, Julie; Striepe, Kristina; Ott, Christian; Martirosian, Petros; Schiffer, Mario; Uder, Michael; Schmieder, Roland (American Journal of Nephrology, 2021)
Background: Alteration in kidney perfusion is an early marker of renal damage. The purpose of this study was to evaluate if changes in renal blood flow (RBF) could be detected using MRI with arterial spin labeling (ASL) technique. Methods: RBF as assessed by cortical (CRBF), medullary, and total renal blood flow (TRBF) were measured by MRI with arterial spin labeling (ASL-MRI) using flow-sensitive alternating inversion recovery true fast imaging with steady-state precession sequence. In 11 normotensive healthy individuals (NT) and 11 hypertensive patients (HT), RBF was measured at baseline and after both feet were covered with cold ice packs (cold pressor test) that activates the sympathetic nervous system. In another experiment, RBF was measured in 10 patients with CKD before and after a pharmacological intervention. We compared RBF measurements between the 3 study populations. Results: A significant reduction in CRBF (p = 0.042) and a trend in TRBF (p = 0.053) were observed in response to the activation of the sympathetic nervous system. A trend toward reduction of CRBF (p = 0.051) and TRBF (p = 0.059) has been detected after pharmacological intervention. TRBF was significantly lower in patients with HT and CKD patients compared to NT individuals (NT vs. HT, p = 0.014; NT vs. CKD, p = 0.004). TRBF was lower in patients with CKD compared to HT (p = 0.047). Conclusion: Our data indicate that both acute and short-term changes in RBF could be detected using ASL-MRI. We were able to detect differences in RBF between healthy and diseased individuals by needing only small sample size per group. Thus, ASL-MRI offers an advantage in conducting clinical trials compared to other technologies.
CRIS-Team Scopus Importer:2021-04-02
Keywords: ASL-MRI; Cold pressor test; Renal blood flow

DETECTION OF CHANGES IN RENAL BLOOD FLOW USING ARTERIAL SPIN LABELING MRI - Kannenkeril, Dennis; Janka, Rolf Matthias; Bosch, Agnes; Jung, Susanne; Kolwelter, Julie; Striepe, Kristina; Ott, Christian; Martirosian, Petros; Schiffer, Mario; Uder, Michael; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2021)
CRIS-Team WoS Importer:2021-07-30

Development and Evaluation of a Semi-automated Segmentation Tool and a Modified Ellipsoid Formula for Volumetric Analysis of the Kidney in Non-contrast T2-Weighted MR Images - Seuß, Hannes; Janka, Rolf Matthias; Pruemmer, Marcus; Hammon, Rebecca; Theis, Ragnar; Sandmair, Martin; Amann, Kerstin Ute; Bäuerle, Tobias; Uder, Michael; Hammon, Matthias; Cavallaro, Alexander Josef (Journal of Digital Imaging, 2017)
Volumetric analysis of the kidney parenchyma provides additional information for the detection and monitoring of various renal diseases. Therefore the purposes of the study were to develop and evaluate a semi-automated segmentation tool and a modified ellipsoid formula for volumetric analysis of the kidney in non-contrast T2-weighted magnetic resonance (MR)-images. Three readers performed semi-automated segmentation of the total kidney volume (TKV) in axial, non-contrast-enhanced T2-weighted MR-images of 24 healthy volunteers (48 kidneys) twice. A semi-automated threshold-based segmentation tool was developed to segment the kidney parenchyma. Furthermore, the three readers measured renal dimensions (length, width, depth) and applied different formulas to calculate the TKV. Manual segmentation served as a reference volume. Volumes of the different methods were compared and time required was recorded. There was no significant difference between the semi-automatically and manually segmented TKV (p = 0.31). The difference in mean volumes was 0.3 ml (95% confidence interval (CI), -10.1 to 10.7 ml). Semi-automated segmentation was significantly faster than manual segmentation, with a mean difference = 188 s (220 vs. 408 s); p < 0.05. Volumes did not differ significantly comparing the results of different readers. Calculation of TKV with a modified ellipsoid formula (ellipsoid volume × 0.85) did not differ significantly from the reference volume; however, the mean error was three times higher (difference of mean volumes -0.1 ml; CI -31.1 to 30.9 ml; p = 0.95). Applying the modified ellipsoid formula was the fastest way to get an estimation of the renal volume (41 s). Semi-automated segmentation and volumetric analysis of the kidney in native T2-weighted MR data delivers accurate and reproducible results and was significantly faster than manual segmentation. Applying a modified ellipsoid formula quickly provides an accurate kidney volume.
EVALuna2:14622

Diagnostic accuracy and interobserver variability of Dynamic Vascular Pattern (DVP) in primary liver malignancies - A simple semiquantitative tool for the analysis of contrast enhancement patterns - Schellhaas, B.; Waldner, Maximilian; Goertza, R. S.; Vitali, Francesco; Kielisch, Ch.; Pfeifer, Lukas; Strobel, Deike; Janka, Rolf Matthias; Neurath, Markus; Wildner, Dane (Clinical Hemorheology and Microcirculation, 2017)
Contrast-enhanced ultrasound (CEUS) is a valuable tool in the diagnostic approach of focal liver lesions, but occasionally subjective and observer-dependent. Semiquantitative evaluation of dynamic CEUS (DCEUS) with standardised software programmes such as Dynamic Vascular Pattern (DVP) could help to improve diagnostic accuracy and objectivity in liver tumour assessment.The present study aimed at evaluation of diagnostic accuracy of DVP in a clinical setting.DVP images of 52 focal liver lesions [30 hepatocellular carcinomas (HCCs), 15 intrahepatic cholangiocellular carcinomas (ICCs), 7 focal nodular hyperplasias (FNHs)] were analysed by four blinded observers with different levels of CEUS-experience. Diagnostic accuracies for the assessment of dignity and entity were evaluated.Mean sensitivity, specificity, positive and negative predictive value for detection of malignancy with DVP were 48.4% /67.8% /92.7% and 29.3%, respectively. Total diagnostic accuracies for dignity/entity were 63.9% /38.5% (HCC: 58.3% /25.8%; ICC: 73.3% /50%; FNH: 67.9% /67.9%). Interreader-agreement was moderate (?= 0.42-0.58). Differential diagnosis between ICC and HCC was most challenging.Although developed to improve diagnostic accuracy and objectivity in the assessment of focal liver lesions, DVP alone seems insufficient for differential diagnosis of HCC, ICC and FNH and cannot replace the skills of an experienced observer.
EVALuna2:14711

Diagnostic Accuracy of an MRI Protocol of the Knee Accelerated Through Parallel Imaging in Correlation to Arthroscopy - Schnaiter, Johannes Walter; Roemer, Frank; Mckenna-Kuettner, Axel; Patzak, Hans-Joachim; May, Matthias; Janka, Rolf Matthias; Uder, Michael; Wüst, Wolfgang (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2018)
PURPOSE: Parallel imaging allows for a considerable shortening of examination times. Limited data is available about the diagnostic accuracy of an accelerated knee MRI protocol based on parallel imaging evaluating all knee joint compartments in a large patient population compared to arthroscopy. MATERIALS AND METHODS: 162 consecutive patients with a knee MRI (1.5 T, Siemens Aera) and arthroscopy were included. The total MRI scan time was less than 9 minutes. Meniscus and cartilage injuries, cruciate ligament lesions, loose joint bodies and medial patellar plicae were evaluated. Sensitivity (SE), specificity (SP), positive predictive value (PPV), and negative predictive value (NPV), as well as diagnostic accuracy were determined. RESULTS: For the medial meniscus, the values were: SE 97 %, SP 88 %, PPV 94 %, and NPV 94 %. For the lateral meniscus the values were: SE 77 %, SP 99 %, PPV 98 %, and NPV 89 %. For cartilage injuries the values were: SE 72 %, SP 80 %, PPV 86 %, and NPV 61 %. For the anterior cruciate ligament the values were: SE 90 %, SP 94 %, PPV 77 %, and NPV 98 %, while all values were 100 % for the posterior cruciate ligament. For loose bodies the values were: SE 48 %, SP 96 %, PPV 62 %, and NPV 93 %, and for the medial patellar plicae the values were: SE 57 %, SP 88 %, PPV 18 %, and NPV 98 %. CONCLUSION: A knee MRI examination with parallel imaging and a scan time of less than 9 minutes delivers reliable results with high diagnostic accuracy. KEY POINTS: · An accelerated knee MRI protocol with parallel imaging allows for high diagnostic accuracy.. · Especially meniscal and cruciate ligament injuries are well depicted.. · Cartilage injuries seem to be overestimated.. CITATION FORMAT: · Schnaiter JW, Roemer F, McKenna-Kuettner A et al. Diagnostic Accuracy of an MRI Protocol of the Knee Accelerated Through Parallel Imaging in Correlation to Arthroscopy. Fortschr Röntgenstr 2018; 190: 265 - 272.
EVALuna2:34702

Difference in renal parenchymal perfusion after renal denervation comparing treated vs. non-treated arteries - Schmieder, R. S.; Schmid, Axel; Janka, Rolf Matthias; Schmieder, Roland; Ott, Christian; Uder, Michael (EUROPEAN HEART JOURNAL, 2018)
CRIS-Team WoS Importer:2019-03-15

Differentiating Benign and Malignant Breast Lesions in Diffusion Kurtosis MRI: Does the Averaging Procedure Matter? - Pistel, Mona; Laun, Frederik Bernd; Bickelhaupt, Sebastian; Dada, Anes; Weiland, Elisabeth; Niederdränk, Torsten; Uder, Michael; Janka, Rolf Matthias; Wenkel, Evelyn; Ohlmeyer, Sabine (Journal of Magnetic Resonance Imaging, 2022)
Background: Diffusion kurtosis imaging (DKI) is used to differentiate between benign and malignant breast lesions. DKI fits are performed either on voxel-by-voxel basis or using volume-averaged signal. Purpose: Investigate and compare DKI parameters' diagnostic performance using voxel-by-voxel and volume-averaged signal fit approach. Study type: Retrospective. Study population: A total of 104 patients, aged 24.1–86.4 years. Field Strength/Sequence: A 3 T Spin-echo planar diffusion-weighted sequence with b-values: 50 s/mm2, 750 s/mm2, and 1500 s/mm2. Dynamic contrast enhanced (DCE) sequence. Assessment: Lesions were manually segmented by M.P. under supervision of S.O. (2 and 5 years of experience in breast MRI). DKI fits were performed on voxel-by-voxel basis and with volume-averaged signal. Diagnostic performance of DKI parameters (Formula presented.) (kurtosis corrected diffusion coefficient) and kurtosis (Formula presented.) was compared between both approaches. Statistical Tests: Receiver operating characteristics analysis and area under the curve (AUC) values were computed. Wilcoxon rank sum and Students t-test tested DKI parameters for significant (P <0.05) difference between benign and malignant lesions. DeLong test was used to test the DKI parameter performance for significant fit approach dependency. Correlation between parameters of the two approaches was determined by Pearson correlation coefficient. Results: DKI parameters were significantly different between benign and malignant lesions for both fit approaches. Median benign vs. malignant values for voxel-by-voxel and volume-averaged approach were 2.00 vs. 1.28 ((Formula presented.) in μm2/msec), 2.03 vs. 1.26 ((Formula presented.) in μm2/msec), 0.54 vs. 0.90 ((Formula presented.)), 0.55 vs. 0.99 ((Formula presented.)). AUC for voxel-by-voxel and volume-averaged fit were 0.9494 and 0.9508 ((Formula presented.)); 0.9175 and 0.9298 ((Formula presented.)). For both, AUC did not differ significantly (P = 0.20). Correlation of values between the two approaches was very high (r = 0.99 for (Formula presented.) and r = 0.97 for (Formula presented.)). Data Conclusion: Voxel-by-voxel and volume-averaged signal fit approach are equally well suited for differentiating between benign and malignant breast lesions in DKI. Evidence Level: 3. Technical Efficacy: Stage 3.
CRIS-Team Scopus Importer:2022-03-25
Keywords: breast lesions; diffusion kurtosis fitting; diffusion magnetic resonance imaging

Diffusion kurtosis imaging does not improve differentiation performance of breast lesions in a short clinical protocol - Palm, Theresa; Wenkel, Evelyn; Ohlmeyer, Sabine; Janka, Rolf Matthias; Uder, Michael; Weiland, Elisabeth; Bickelhaupt, Sebastian; Ladd, Mark E.; Zaitsev, Maxim; Hensel, Bernhard; Laun, Frederik Bernd (Magnetic Resonance Imaging, 2019)
Background: Diffusion weighted magnetic resonance imaging (DWI) is known to differentiate between malignant and benign lesions via the apparent diffusion coefficient (ADC). Here, the value of diffusion kurtosis imaging (DKI) for differentiation and further characterization of benign and malignant breast lesions and their subtypes in a clinically feasible protocol is investigated. Material and methods: This study included 85 patients (with 68 malignant and 73 benign lesions) who underwent 3 T breast DWI using three b values (50, 750, 1500 s/mm2), with a total measurement time < 5 min. ADC maps were calculated from b values 50, 750 s/mm2. The diffusion kurtosis model was fitted to the diffusion weighted images, yielding in each lesion the average kurtosis-corrected diffusion coefficient DK and mean kurtosis K. Histopathology was obtained of radiologically suspicious lesions; follow-up scans were used as a standard of reference for benign appearing lesions. Receiver operating characteristic curves were used to evaluate the parameters' diagnostic performance for differentiation of lesion types and grades. The difference in diffusion parameters between subgroups was analysed statistically using the Wilcoxon rank sum test and Kruskal-Wallis test, applying a Bonferroni correction for multiple testing where necessary. Results: ADC, DK and K showed significant differences between malignant and benign lesions (p < 10−5). All parameters had similar areas under the curve (AUC) (ADC: 0.92, DK: 0.91, K: 0.89) for differentiation of malignant and benign lesions. Sensitivity was highest for ADC (ADC: 0.96, DK: 0.94, K: 0.93), as well as specificity (ADC: 0.85, DK: 0.82, K: 0.82). ADC and DK showed significant differences between tumor histologic grades (p = 6.8⋅10−4, p = 6.6 · 10−5, respectively), whereas K did not (p = 0.99). All three parameters differed significantly between subtypes of benign lesions (ADC: p < 10−5, DK: p< 10−5, K: p = 4.1·10−4), but not between subtypes of malignant lesions (ADC: p = 0.21, DK: p = 0.25, K: p = 0.08). Conclusion: DKI parameters and conventional ADC can differentiate between malignant and benign lesions. Differentiation performance was best for ADC. Different tumor grades were significantly different in ADC and DK, which may have an impact on therapy planning and monitoring. In our study, K did not add value to the diagnostic performance of DWI in a clinical setting.
CRIS-Team Scopus Importer:2019-08-30
Keywords: Breast neoplasms; Diagnostic imaging; Diffusion kurtosis imaging; Diffusion magnetic resonance imaging; Neoplasms by histologic type

Diffusion-weighted breast imaging. Clinical implementation procedure - Wenkel, Evelyn; Uder, Michael; Janka, Rolf Matthias (Radiologe, 2014)
Diffusion-weighted imaging (DWI) of the breast provides additional contrast information in breast magnetic resonance imaging (MRI). The DWI procedure can easily be implemented in the routine breast MRI protocol with little time expenditure regarding image acquisition and evaluation. Evaluation of the DW images can be performed with or without the routine breast MRI sequences (T2w and T1w with contrast material) but evaluation in combination with the routine program is highly recommended. Objective analysis of the tissue diffusion can be achieved by calculating the apparent diffusion coefficient (ADC) value with the scanner software. The choice of the DW sequence, evaluation and determination of the ADC threshold to differentiate between benign and malignant lesions should be scanner adapted. The use of DW imaging qualifies for routine use regarding the differentiation between malignant and benign breast lesions. Non-mass-like lesions and monitoring neoadjuvant chemotherapy can also be evaluated with DW sequences. The benefit of the additional information from DW-MR mammography to characterize non-mass-like lesions and in the course of neoadjuvant chemotherapy remains unclear to date.
EVALuna2:14377

Diffusion-Weighted Imaging for Skin Pathologies of the Breast—A Feasibility Study - Skwierawska, Dominika; Laun, Frederik Bernd; Wenkel, Evelyn; Kapsner, Lorenz; Janka, Rolf Matthias; Uder, Michael; Ohlmeyer, Sabine; Bickelhaupt, Sebastian (Diagnostics, 2024)
Several breast pathologies can affect the skin, and clinical pathways might differ significantly depending on the underlying diagnosis. This study investigates the feasibility of using diffusion-weighted imaging (DWI) to differentiate skin pathologies in breast MRIs. This retrospective study included 88 female patients who underwent diagnostic breast MRI (1.5 or 3T), including DWI. Skin areas were manually segmented, and the apparent diffusion coefficients (ADCs) were compared between different pathologies: inflammatory breast cancer (IBC; n = 5), benign skin inflammation (BSI; n = 11), Paget’s disease (PD; n = 3), and skin-involved breast cancer (SIBC; n = 11). Fifty-eight women had healthy skin (H; n = 58). The SIBC group had a significantly lower mean ADC than the BSI and IBC groups. These differences persisted for the first-order features of the ADC (mean, median, maximum, and minimum) only between the SIBC and BSI groups. The mean ADC did not differ significantly between the BSI and IBC groups. Quantitative DWI assessments demonstrated differences between various skin-affecting pathologies, but did not distinguish clearly between all of them. More extensive studies are needed to assess the utility of quantitative DWI in supplementing the diagnostic assessment of skin pathologies in breast imaging.
CRIS-Team Scopus Importer:2024-05-24
Keywords: apparent diffusion coefficient; breast cancer; diffusion-weighted imaging; magnetic resonance imaging; skin cancer

Diffusion-weighted MR imaging of benign and malignant breast lesions before and after contrast enhancement - Janka, Rolf Matthias; Hammon, Matthias; Geppert, C.; Nothhelfer, A.; Uder, Michael; Wenkel, Evelyn (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Many publications describe the use of diffusion-weighted imaging (DWI) in breast MRI. This article addresses the question of when to apply the DWI sequence in the course of the scan protocol. The effect of T1-shortening contrast media (CM) on the ADC values of breast lesions is investigated.Data were acquired on a 1.5 T scanner. 60 patients with 79 lesions (20 benign, 59 malignant) were included. The DWI sequence (4 mm slice thickness, b-values: 50, 400, 800) was applied before and after CM administration. Before calculating the ADC map, the b50, b400 and b800 series were analyzed concerning lesion displacement. ADC values before and after CM application were compared.The mean lesion size was 1.5 ± 0.8 cm. On the basis of the b50 and b400 measurements, the mean ADC value of benign lesions was 1.89 ± 0.30 × 10-3 mm2/s before and 1.85 ± 0.28 ×10-3 mm2/s after CM administration. The consecutive values for two pure mucinous carcinomas were 1.88 × 10-3 mm2/s and 1.81 × 103 mm2/s and for the remaining malignant lesions 1.00 ± 0.18 × 10-3 mm2/s and 0.88 ± 0.21 × 10-3 mm2. On the basis of the b50, b400 and b800 measurements, the mean ADC value of benign lesions was 1.99 ± 0.37 × 10-3 mm2/s before and 1.97 ± 0.30 × 10-3 mm2/s after CM application, whereas the mean ADC value of the malignant lesions was 0.90 ± 0.14 × 10-3 mm2/s before and 0.80 ± 0.14 × 10-3 mm2/s after CM application. While there was no significant change for benign lesions, the ADC value decrease in post-contrast malignant lesions was highly significant.DWI after CM is possible and even leads to slightly better lesion discrimination between benign and malignant. However, further studies need to be performed to verify this. Citation Format: o?Janka R, Hammon M, Geppert C et al. Diffusion-Weighted MR Imaging of Benign and Malignant Breast Lesions Before and After Contrast Enhancement. Fortschr Röntgenstr 2014; 186: 130 - 135.
EVALuna2:14329

Disordered Eating and Exercise Dependence in Endurance Athletes - Zeulner, Bernd; Ziemainz, Heiko; Beyer, Christian; Hammon, Matthias; Janka, Rolf Matthias (Advances in Physical Education, 2016)
UnivIS-Import:2016-06-01:Pub.2016.phil.dps.iss.lsw.disord
Keywords: Exercise; Addiction; Dependence; Endurance; Athletes

Dose reduction potential of iterative reconstruction algorithms in neck CTA-a simulation study - Ellmann, Stephan; Kammerer, Ferdinand; Allmendinger, Thomas; Brand, Michael; Janka, Rolf Matthias; Hammon, Matthias; Lell, Michael M.; Uder, Michael; Kramer, Manuel (Dentomaxillofacial Radiology, 2016)
This study aimed to determine the degree of radiation dose reduction in neck CT angiography (CTA) achievable with Sinogram-affirmed iterative reconstruction (SAFIRE) algorithms.10 consecutive patients scheduled for neck CTA were included in this study. CTA images of the external carotid arteries either were reconstructed with filtered back projection (FBP) at full radiation dose level or underwent simulated dose reduction by proprietary reconstruction software. The dose-reduced images were reconstructed using either SAFIRE 3 or SAFIRE 5 and compared with full-dose FBP images in terms of vessel definition. 5 observers performed a total of 3000 pairwise comparisons.SAFIRE allowed substantial radiation dose reductions in neck CTA while maintaining vessel definition. The possible levels of radiation dose reduction ranged from approximately 34 to approximately 90% and depended on the SAFIRE algorithm strength and the size of the vessel of interest. In general, larger vessels permitted higher degrees of radiation dose reduction, especially with higher SAFIRE strength levels. With small vessels, the superiority of SAFIRE 5 over SAFIRE 3 was lost.Neck CTA can be performed with substantially less radiation dose when SAFIRE is applied. The exact degree of radiation dose reduction should be adapted to the clinical question, in particular to the smallest vessel needing excellent definition.
EVALuna2:14595

Dynamic study of the finger interphalangeal joint volar plate—motion analysis with magnetic resonance cinematography and histologic comparison - Lutter, Christoph; Kürten, Stefanie; Geppert, Carol-Immanuel; Mittelmeier, Wolfram; Klinder, Annett; Söder, Stephan; Roemer, Frank; Uder, Michael; Janka, Rolf Matthias; Bayer, Thomas (Skeletal Radiology, 2023)
Objective: We aimed to further improve knowledge about volar plate (VP) motion of the finger proximal interphalangeal joint (PIP), by analyzing the dynamic VP shape during a full range of finger flexion using magnetic resonance cinematography of the fingers (MRCF), and to compare the results with anatomical cross sections from cadaver specimens. Materials and methods: The dynamic sagittal VP shape was visualized with MRCF in a total number of 23 healthy volunteers. The length, angle, and thickness as well as the contact length of the VP to the PIP joint base were measured. Statistical analysis included t-test or rank-sum testing. Anatomical cross sections with differing degrees of PIP joint flexion were obtained from 12 cadaver specimens (fingers) for comparison. Results: Significant positive correlations between PIP joint flexion angle and VP area, length, depth and the VP contact length were found. This matched histologically to fiber rearrangements especially within the loose third VP layer. Conclusion: Our study analyzed the full range of motion dynamic VP shape of the PIP joint using MRCF. This contributes to a more precise understanding of the complex interaction of the VP with the PIP joint and may facilitate evaluation of clinical cases such as VP avulsion or pulley rupture.
CRIS-Team Scopus Importer:2023-02-17
Keywords: Dislocation; Injury; Microsurgery; MRI; Ultrasound

Effect of Compression Garments on the Development of Edema and Soreness in Delayed-Onset Muscle Soreness (DOMS) - Heiß, Rafael; Hotfiel, Thilo; Kellermann, Marion; May, Matthias; Wüst, Wolfgang; Janka, Rolf Matthias; Nagel, Armin M.; Uder, Michael; Hammon, Matthias (Journal of Sports Science and Medicine, 2018)
Delayed-onset muscle soreness (DOMS), an ultrastructural muscle injury, is one of the most common reasons for impaired muscle performance. The purpose of this study was to investigate the influence of sport compression garments on the development of exercise-induced intramuscular edema in the context of DOMS. DOMS was induced in 15 healthy participants. The participants performed a standardized eccentric exercise of the calf muscles. Magnetic resonance imaging (MRI) was performed at baseline and 60h after exercise (T2-weighted signal intensity and T2 relaxation time was evaluated in each compartment and the intramuscular edema in the medial head of the gastrocnemius muscle was segmented). After the exercise, a conventional compression garment (18-21 mmHg) was placed on one randomized calf for 60h. The level of muscle soreness was evaluated using a visual analogue pain scale. T2-weighted signal intensity, T2 relaxation time and intramuscular edema showed a significant interaction for time with increased signal intensities/intramuscular edema in the medial head of the gastrocnemius muscle at follow-up compared to baseline. No significant main effect for compression or interaction between time and limb occurred. Further, no significant differences in the soleus muscle and the lateral head of the gastrocnemius muscle were noted between limbs or over time. After exercise, there was significantly increased muscle soreness in both lower legs in resting condition and when going downstairs and a decreased range of motion in the ankle joint. No significant difference was observed between the compressed and the non-compressed calf. Our results indicate that wearing conventional compression garments after DOMS has been induced has no significant effect on the development of muscle edema, muscle soreness, range of motion and calf circumference.
EVALuna2:34690

Effect of Flat-Knitted Medical Compression Stockings on Venous Malformations - Li, Yi; Muekke, Antje; Rother, Ulrich; Janka, Rolf Matthias; Uder, Michael; Lang, Werner; Heiß, Rafael (Journal of Clinical Medicine, 2023)
Venous malformations are one of the most common vascular anomalies. Our study aimed to investigate the effect of medical compression stockings of class I and II on the volume of venous malformations. Patients with venous malformations on upper or lower extremities were enrolled. They wore flat-knitted medical compression stockings of class I and II in a randomized order for four weeks each. Magnetic resonance imaging (MRI) and perometry were performed with and without wearing compression stockings. The 12-Item Short Form Survey (SF-12) questionnaire was performed before and after wearing compression stockings for four weeks each. A total of 18 patients completed the evaluations. Both compression classes showed a significant reduction of the volume of the venous malformations in the lesion itself based on MRI in comparison with baseline (both p < 0.001). Measurements taken with perometry did not reveal a significant difference in comparison to baseline (p = 0.09 and p = 0.22). The results of the SF-12 questionnaire demonstrated no significant differences before and after wearing the compression stockings of class I or class II for four weeks or between the two classes of compression therapy. Our results indicate that wearing medical compression stockings of both class I and class II significantly reduces the volume of venous malformation, without compromising the quality of life, while the effect of class II compression stockings on volume reduction was significantly better than that of class I.
CRIS-Team Scopus Importer:2023-04-28
Keywords: compression stockings; magnetic resonance imaging; perometry; quality of life; T2-weighted imaging; venous malformation

Effects of video-based patient preparation for MRI on clinical processes and patient experience. - Madl, Janika; Janka, Rolf Matthias; Bay, Susanne; Sturmbauer, Sarah; Rohleder, Nicolas (European Journal of Radiology, 2022)
To determine whether video-based informational or relaxational preparation reduces the number of unexpected patient-related events and scan duration more efficiently, and to assess how patients evaluate the interventions. We randomized 142 adult patients (mean age: 48 ± 16 years) to three groups. The control group (n = 48, 33.8 %) received standard care. The intervention groups watched an informational (n = 50, 35.2 %) or relaxational (n = 44, 31.0 %) video while awaiting their MRI examination. We recorded scan duration, number of motion artifacts/sequence repetitions, and patient-related incidents (e.g., interruptions, premature termination). Subjective evaluation of the interventions was provided by the patients after MRI completion. Mean scan duration for the control, relaxation, and information group was 39.38 ± 16.62 min, 32.59 ± 11.67 min, and 34.54 ± 11.91 min. Compared to the control group, scan duration was significantly shorter in the relaxation, but not in the information group (relaxation vs control: p =.019; information vs control: p =.082). The information and relaxation group did not differ significantly (p =.704). In 35 (24.6 %) patients, one or more sequences were repeated; incidents occurred in six (4.2 %) patients. Neither the frequency of repeated sequences nor incidents differed between the groups (all p >.239). Patients evaluated both videos very positively; the information video received even better evaluations (all p <.027). Additional preparation, especially information, is perceived very positively by patients and at least relaxational preparation may have a positive impact on clinical operations. PURPOSE METHODS RESULTS CONCLUSION

Einfluss neuer Techniken in der Bildgebung der Niere - Uder, Michael; Heinrich, Marc Christopher; Jäger, Florian; Hornegger, Joachim; Schmieder, Roland; Janka, Rolf Matthias (Nephrologe, 2009)
Computed tomography and magnetic resonance imaging have developed very rapidly in recent years. Today these methods are capable not only of morphological assessment of the kidneys but also provide data of a functional nature. Urography by MRI and CT have long been established in clinical routine. Other techniques such as blood level oxygenation-dependent (BOLD), diffusion-weighted, and renal perfusion imaging using MRI or CT are used almost exclusively for research purposes, but they also have many possibilities for renal applications under study conditions in diagnostics and for monitoring vascular and parenchymatous disorders. © 2009 Springer-Verlag.

Erratum to: Stress examination of flexor tendon pulley rupture in the crimp grip position: a 1.5-Tesla MRI cadaver study - Bayer, Thomas; Fries, Simon; Schweizer, Andreas; Schoeffl, Isabelle; Janka, Rolf Matthias; Bongartz, Georg (Skeletal Radiology, 2015)
EVALuna2:14346

Evaluation of finger A3 pulley rupture in the crimp grip position-a magnetic resonance imaging cadaver study - Bayer, Thomas; Adler, Werner; Schweizer, Andreas; Schoeffl, Isabelle; Uder, Michael; Janka, Rolf Matthias (Skeletal Radiology, 2015)
The correct diagnosis of an A3 pulley rupture is challenging for musculoskeletal radiologists. An A3 pulley rupture should in theory influence the shape of the proximal interphalangeal joint volar plate (VP) and the amount of bowstringing at level of the VP during finger flexion. The purpose of this study was to perform MRI with metric analysis of the VP configuration and VP bowstringing in cadaver fingers in the crimp grip position and to determine cut points for A3 pulley rupture.MRI in the crimp grip position was performed in 21 cadaver fingers with artificially created flexor tendon pulley tears (fingers with A3 pulley rupture n = 16, fingers without A3 pulley rupture n = 5). The distances of the translation of the VP relative to the middle phalanx base, the distances between the flexor tendons and the VP body, and the distances between the flexor tendon and bone (TB) were measured.Statistical analysis showed significantly lower VP translation distances and significantly higher VP tendon distances if the A3 pulley was ruptured. A2 TB and A4 TB distances did not differ significantly in specimens with and without A3 pulley rupture. The optimal cut points for A3 pulley rupture were a VP translation distance <2.8 mm and a VP tendon distance >1.4 mm.Reduction of the VP translation distance and augmentation of the VP tendon distance are suitable indirect signs of A3 pulley rupture.
EVALuna2:5492

Evaluation of finger cartilage composition in recreational climbers with 7 Tesla T2 mapping magnetic resonance imaging - Bayer, Thomas; Brockhoff, Marie-Jo; Nagel, Armin Michael; Adler, Werner; Lutter, Christoph; Janka, Rolf Matthias; Heiß, Rafael; Uder, Michael; Roemer, Frank (Frontiers in Sports and Active Living, 2023)
Purpose: Sport climbing may lead to tissue adaptation including finger cartilage before apparent surface damage is detectable. The main aim was to assess finger cartilage composition with T2 mapping in young, active climbers and to compare the results to a non-climbers' collective. A secondary aim was to compare whether differences in cartilage T2 times are observed between older vs. younger volunteers. Methods and materials: 7 Tesla MRI of the fingers Dig.2–4 was performed using a multi-echo spin echo sequence. Manual segmentation of 3 ROIs at the metacarpal heads, 1 ROI at the base phalanx and 1 ROI at the proximal interphalangeal joint was performed. Included were 13 volunteers without history of trauma who are regularly performing climbing activities as a recreational sport (>20 h/month). These were age-matched with 10 control subjects not performing climbing activities. Results: Mean age was 32.4 years for the climbing group and 25.8 years for the controls. Mean T2 values for the 5 different ROIs were 42.2 ± 7.8 msec for climbers and 41.4 ± 6.8 msec for non-climbers. No significant differences were observed for T2 values between both groups. However, higher age had a significant impact on T2 values for all assessed ROIs (higher age 44.2 ± 9.5, younger age 32.9 ± 5.7, p = 0.001). Discussion: This study evaluated the cartilage composition of young, engaged climbers with a T2 mapping MRI technique with the purpose to depict early onset joint changes. No negative impact on cartilage composition due to the sport activity was found, whereas age-related effects on the cartilage seemed to be more prominent.
CRIS-Team Scopus Importer:2023-10-20
Keywords: cartilage; climbing; finger; magenetic resonance imaging; mapping

Evaluation of novice reader diagnostic performance in coronary CT angiography using an advanced cardiac software package - Dankerl, Peter; Hammon, Matthias; Tsymbal, Alexey; Achenbach, Stephan; Uder, Michael; Janka, Rolf Matthias; Cavallaro, Alexander Josef (International Journal of Computer Assisted Radiology and Surgery, 2014)
The purpose of this research was to evaluate whether a commercially available advanced cardiac software package for coronary CT angiography (CTA) interpretation may reliably assist inexperienced readers to screen for significant coronary artery stenoses.Coronary CTA data sets of 61 consecutive patients with suspected coronary artery disease were evaluated by three novice readers with no experience in cardiac CT interpretation. In the first 15 patients, the novice readers were trained to use the advanced cardiac software package (includes automatic detection of coronary vessels, curved MPR and VRT reconstructions and a measurement too) knowing the results of an expert read. In the next 46 patients, the novice readers had to state whether there is a significant coronary artery stenosis ([Formula: see text]50 %) and if they are confident with their diagnosis. The results of the novice readers were compared to the expert read.The 46 coronary CTA data sets contained 184 vessels with 15 stenoses in 9 patients. On a per-vessel analysis, novice reader 1/2/3 demonstrated 60 %/100 %/ 93% sensitivity, and 98 %/90 %/86 % specificity. Per patient, the readers diagnosed 36/28/29 cases correctly as free of stenoses, 6/9/8 correctly as having at least one stenosis, missed 3/0/1 cases with a stenosis and overdiagnosed 1/9/8 patients. Cohen's kappa values for the three readers versus the expert were 0.60, 0.61 and 0.54. The three novice readers felt confident in the diagnosis of 36/33/30 patients. In these patients, they missed one significant stenosis, showed a sensitivity of 100 %/100 %/75 % and a specificity of 100 %/92 %/88 %.The evaluated advanced cardiac software package successfully assists novice readers in interpreting coronary CTA data sets especially in ruling out significant coronary artery stenosis.
EVALuna2:11866

Expertenempfehlung zur Magnetresonanztomographie bei Muskelerkrankungen - Zeng, Rachel; Schlaeger, Sarah; Türk, Matthias; Baum, Thomas; Deschauer, Marcus; Janka, Rolf Matthias; Karampinos, Dimitrios; Kassubek, Jan; Keller-Yamamura, Sarah; Kornblum, Cornelia; Lehmann, Helmar; Lichtenstein, Thorsten; et al. (Der Nervenarzt, 2024)
Background: Magnetic resonance (MRI) imaging of the skeletal muscles (muscle MRI for short) is increasingly being used in clinical routine for diagnosis and longitudinal assessment of muscle disorders. However, cross-centre standards for measurement protocol and radiological assessment are still lacking. Objectives: The aim of this expert recommendation is to present standards for the application and interpretation of muscle MRI in hereditary and inflammatory muscle disorders. Methods: This work was developed in collaboration between neurologists, neuroradiologists, radiologists, neuropaediatricians, neuroscientists and MR physicists from different university hospitals in Germany. The recommendations are based on expert knowledge and a focused literature search. Results: The indications for muscle MRI are explained, including the detection and monitoring of structural tissue changes and oedema in the muscle, as well as the identification of a suitable biopsy site. Recommendations for the examination procedure and selection of appropriate MRI sequences are given. Finally, steps for a structured radiological assessment are presented. Conclusions: The present work provides concrete recommendations for the indication, implementation and interpretation of muscle MRI in muscle disorders. Furthermore, it provides a possible basis for the standardisation of the measurement protocols at all clinical centres in Germany.
CRIS-Team Scopus Importer:2024-05-10
Keywords: Diagnostics; Muscle MRI; Myopathy; Myositis; Semi-quantitative assessment scales

Expertenempfehlung zur Magnetresonanztomographie bei Muskelerkrankungen - Zeng, Rachel; Schlaeger, Sarah; Türk, Matthias; Baum, Thomas; Deschauer, Marcus; Janka, Rolf Matthias; Karampinos, Dimitrios; Kassubek, Jan; Keller-Yamamura, Sarah; Kornblum, Cornelia; Lehmann, Helmar; Lichtenstein, Thorsten; et al. (Die Radiologie, 2024)
BACKGROUND: Magnetic resonance (MRI) imaging of the skeletal muscles (muscle MRI for short) is increasingly being used in clinical routine for diagnosis and longitudinal assessment of muscle disorders. However, cross-centre standards for measurement protocol and radiological assessment are still lacking. OBJECTIVES: The aim of this expert recommendation is to present standards for the application and interpretation of muscle MRI in hereditary and inflammatory muscle disorders. METHODS: This work was developed in collaboration between neurologists, neuroradiologists, radiologists, neuropaediatricians, neuroscientists and MR physicists from different university hospitals in Germany. The recommendations are based on expert knowledge and a focused literature search. RESULTS: The indications for muscle MRI are explained, including the detection and monitoring of structural tissue changes and oedema in the muscle, as well as the identification of a suitable biopsy site. Recommendations for the examination procedure and selection of appropriate MRI sequences are given. Finally, steps for a structured radiological assessment are presented. CONCLUSIONS: The present work provides concrete recommendations for the indication, implementation and interpretation of muscle MRI in muscle disorders. Furthermore, it provides a possible basis for the standardisation of the measurement protocols at all clinical centres in Germany.
EVALuna2:566089

Extent of simultaneous radiation dose and iodine reduction at stable image quality in computed tomography of the chest: A systematic approach using automated tube voltage adaption and iterative reconstructions - Eller, Achim; Wüst, Wolfgang; Saake, Marc; Ellmann, Stephan; Kämmerer, Nadine; Hammon, Matthias; Janka, Rolf Matthias; Uder, Michael; May, Matthias (Medicine, 2018)
BACKGROUND: Aim of this study was to systematically combine tube voltage adaptation and iterative reconstructions for reduction of iodine and radiation dose. METHODS: Settings for the study protocol were evaluated in ex-ante trials to provide image quality that is comparable to a reference protocol at 120 kV with tube current modulation. Consecutive patients were randomized to undergo computed tomography (CT) of the chest using the study protocol (n = 62) or reference protocol (n = 50). Objective and subjective image quality was assessed and compared. RESULTS: Tube voltage was decreased to 100 kV in 47 patients and to 80 kV in 15 patients in the study group. The iodine dosage (16.1 vs 10.5 g) and the effective radiation dose (3.6 vs 2.5 mSv) were significantly decreased in the study group (both P < .001). Contrast-to-noise ratio was comparable in the pulmonary trunk and increased in the aorta (P < .01). Subjective image quality was comparable without statistically significance. CONCLUSIONS: Simultaneous reductions in iodine dosage and radiation dose by one-third are feasible for CT of the chest.
EVALuna2:34701

Fine needle aspiration cytology of lymph nodes in breast cancer follow-up is a feasible alternative to watchful waiting and to histology - Hammon, Matthias; Dankerl, Peter; Janka, Rolf Matthias; Wachter, David; Hartmann, Arndt; Schulz-Wendtland, Rüdiger; Uder, Michael; Wenkel, Evelyn (BMC Women's Health, 2015)
Early detection of loco-regional breast cancer recurrence improves patients' overall survival, as treatment can be initiated or active treatment can be changed. If a suspicious lymph node is diagnosed during a follow-up exam, surgical excision is often performed. The aim of this study was to evaluate the diagnostic performance of the minor invasive ultrasound-guided fine-needle aspiration cytology (FNAC) in sonomorphologically suspicious lymph nodes in breast cancer follow-up.Between April 2010 and November 2012, we performed ultrasound-guided FNAC in 38 sonographically suspicious lymph nodes of 37 breast cancer follow-up patients. Cytological specimens were evaluated if the sample material was sufficient for diagnosis and if they contained cancer cells. Patients with negative cytology were followed up clinically and sonographically. To evaluate the diagnostic performance we calculated sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) for physical examination, the different sonomorphological malignancy criteria and FNAC.In 36/38 (94.7 %) lymph nodes, the pathologist had enough material to establish a final diagnosis; in 2/38 (5.3 %) lymph nodes, the probe material was non-evaluable during cytology, these 2 were excluded from further statistical evaluation. Cytology revealed malignancy in 21 lymph nodes and showed no evidence for malignancy in 15 lymph nodes. There was no evidence for malignant disease in follow-up exams in the 15 cytologically benign lymph nodes with an average follow-up time of 3 years. The diagnostic performances of physical examination and FNAC were: Sensitivity 52/100 %, specificity 88/100 %, PPV 85/100 %, NPV 60/100 %, respectively.Our preliminary results show that FNAC is a safe and fast diagnostic approach for the evaluation of suspicious lymph nodes in the follow-up of patients with breast cancer and, thus, together with follow-up represents a feasible alternative to surgery.
EVALuna2:6744

Functional ankle instability as a risk factor for osteoarthritis: Using T2-mapping to analyze early cartilage degeneration in the ankle joint of young athletes - Golditz, Tobias; Steib, Simon; Pfeifer, Klaus; Uder, Michael; Gelse, Kolja; Janka, Rolf Matthias; Hennig, Friedrich; Welsch, Götz (Osteoarthritis and Cartilage, 2014)
Objective: The aim of this study was to investigate, using T2-mapping, the impact of functional instability in the ankle joint on the development of early cartilage damage. Methods: Ethical approval for this study was provided. Thirty-six volunteers from the university sports program were divided into three groups according to their ankle status: functional ankle instability (FAI, initial ankle sprain with residual instability); ankle sprain Copers (initial sprain, without residual instability); and controls (without a history of ankle injuries). Quantitative T2-mapping magnetic resonance imaging (MRI) was performed at the beginning ('early-unloading') and at the end ('late-unloading') of the MR-examination, with a mean time span of 27min. Zonal region-of-interest T2-mapping was performed on the talar and tibial cartilage in the deep and superficial layers. The inter-group comparisons of T2-values were analyzed using paired and unpaired t-tests. Statistical analysis of variance was performed. Results: T2-values showed significant to highly significant differences in 11 of 12 regions throughout the groups. In early-unloading, the FAI-group showed a significant increase in quantitative T2-values in the medial, talar regions (. P=0.008, P=0.027), whereas the Coper-group showed this enhancement in the central-lateral regions (. P=0.05). Especially the comparison of early-loading to late-unloading values revealed significantly decreasing T2-values over time laterally and significantly increasing T2-values medially in the FAI-group, which were not present in the Coper- or control-group. Conclusion: Functional instability causes unbalanced loading in the ankle joint, resulting in cartilage alterations as assessed by quantitative T2-mapping. This approach can visualize and localize early cartilage abnormalities, possibly enabling specific treatment options to prevent osteoarthritis in young athletes.
UnivIS-Import:2015-03-09:Pub.2014.phil.dps.iss.psbg.functi
Keywords: Functional ankle instability; Magnetic resonance imaging; Osteoarthritis; Sports medicine; T2-mapping

Haptic Rendering of Soft-Tissue for Training Surgical Procedures at the Larynx - Eixelberger, Thomas; Parchent, Jonas; Janka, Rolf Matthias; Stamminger, Marc; Döllinger, Michael; Wittenberg, Thomas (Bildverarbeitung für die Medizin 2020, Informatik aktuell, 2020)

Highly accelerated, Dixon-based non-contrast MR angiography versus high-pitch CT angiography - Zeilinger, Martin; Giese, Daniel; Schmidt, Michaela; May, Matthias; Janka, Rolf Matthias; Heiß, Rafael; Ammon, Fabian; Achenbach, Stephan; Uder, Michael; Treutlein, Christoph (Radiologia Medica, 2023)
Objectives: To compare a novel, non-contrast, flow-independent, 3D isotropic magnetic resonance angiography (MRA) sequence that combines respiration compensation, electrocardiogram (ECG)-triggering, undersampling, and Dixon water-fat separation with an ECG-triggered aortic high-pitch computed tomography angiography (CTA) of the aorta. Materials and methods: Twenty-five patients with recent CTA were scheduled for non-contrast MRA on a 3 T MRI. Aortic diameters and cross-sectional areas were measured on MRA and CTA using semiautomatic measurement tools at 11 aortic levels. Image quality was assessed independently by two radiologists on predefined aortic levels, including myocardium, proximal aortic branches, pulmonary veins and arteries, and the inferior (IVC) and superior vena cava (SVC). Image quality was assessed on a 5-point Likert scale. Results: All datasets showed diagnostic image quality. Visual grading was similar for MRA and CTA regarding overall image quality (0.71), systemic arterial image quality (p = 0.07–0.91) and pulmonary artery image quality (p = 0.05). Both readers favored MRA for SVC and IVC, while CTA was preferred for pulmonary veins (all p < 0.05). No significant difference was observed in aortic diameters or cross-sectional areas between native MRA and contrast-enhanced CTA (p = 0.08–0.94). Conclusion: The proposed non-contrast MRA enables robust imaging of the aorta, its proximal branches and the pulmonary arteries and great veins with image quality and aortic diameters and cross-sectional areas comparable to that of CTA. Moreover, this technique represents a suitable free-breathing alternative, without the use of contrast agents or ionizing radiation. Therefore, it is especially suitable for patients requiring repetitive imaging.
CRIS-Team Scopus Importer:2023-12-08
Keywords: Angiography; Computed tomography; Follow-up studies; Magnetic resonance imaging

Imaging of muscle injuries in sports medicine - Heiß, Rafael; Janka, Rolf Matthias; Uder, Michael; Hotfiel, Thilo; Gast, Lena; Nagel, Armin Michael; Roemer, Frank (Die Radiologie, 2023)
Background: Early diagnosis of muscle injuries is indispensable in order to initiate appropriate treatment and to facilitate optimal healing.Purpose: The aim of this review is to provide an update on imaging of muscle injuries in sports medicine with a focus on ultrasound and magnetic resonance imaging (MRI) and to present experimental approaches in addition to routine diagnostic procedures.Materials and methods: A PubMed literature search for the years 2012-2022 using the following keywords was performed: muscle, muscle injury, muscle imaging, muscle injury classification, delayed onset muscle soreness, ultrasound, MRI, sodium MRI, potassium MRI, ultra-high-field MRI, injuries of athletes.Results: Imaging is crucial to confirm and assess the extent of sports-related muscle injuries and may help establishing treatment decisions, which directly affect the prognosis. This is of importance when the diagnosis or grade of injury is unclear, when recovery is taking longer than expected, and when interventional or surgical management may be necessary. In addition to established methods such as B-mode ultrasound and H-1-MRI, individual studies show promising approaches to further improve the imaging of muscle injuries in the future. Prior to the integration of contrast-enhanced ultrasound and X-nuclei into clinical routine, additional studies are needed to validate these techniques further.Conclusion: B-mode ultrasound represents an easily available, cost-effective modality for the initial diagnosis of muscle injuries. MRI is still considered the reference standard and enables an accurate morphological assessment of the extent of the injury. There are still no imaging approaches available for the objective determination of the optimal point of return to play.
CRIS-Team WoS Importer:2023-03-24

IMPACT OF CLIMBING ACTIVITY AND AGE ON CARTILAGE STRUCTURAL COMPOSITION OF THE METACARPOPHALANGEAL AND PROXIMAL INTERPHALANGEAL JOINTS AS ASSESSED BY T2 RELAXOMETRY AT 7T MRI - Heiß, Rafael; Bayer, T.; Janka, Rolf Matthias; Brockhoff, Marie-Jo; Uder, Michael; Nagel, Armin Michael; Roemer, Frank (OSTEOARTHRITIS AND CARTILAGE, 2020)
CRIS-Team WoS Importer:2020-05-29

Implementation of a dedicated 1.5 T MR scanner for radiotherapy treatment planning featuring a novel high-channel coil setup for brain imaging in treatment position - Mengling, Veit; Bert, Christoph; Perrin, Rosalind; Masitho, Siti; Weissmann, Thomas; Mansoorian, Sina; Siavooshhaghighi, Hadi; Janka, Rolf Matthias; Doussin, Sylvain; Habatsch, Melanie; Fietkau, Rainer; Putz, Florian (Strahlentherapie und Onkologie, 2020)
Purpose: To share our experiences in implementing a dedicated magnetic resonance (MR) scanner for radiotherapy (RT) treatment planning using a novel coil setup for brain imaging in treatment position as well as to present developed core protocols with sequences specifically tuned for brain and prostate RT treatment planning. Materials and methods: Our novel setup consists of two large 18-channel flexible coils and a specifically designed wooden mask holder mounted on a flat tabletop overlay, which allows patients to be measured in treatment position with mask immobilization. The signal-to-noise ratio (SNR) of this setup was compared to the vendor-provided flexible coil RT setup and the standard setup for diagnostic radiology. The occurrence of motion artifacts was quantified. To develop magnetic resonance imaging (MRI) protocols, we formulated site- and disease-specific clinical objectives. Results: Our novel setup showed mean SNR of 163 ± 28 anteriorly, 104 ± 23 centrally, and 78 ± 14 posteriorly compared to 84 ± 8 and 102 ± 22 anteriorly, 68 ± 6 and 95 ± 20 centrally, and 56 ± 7 and 119 ± 23 posteriorly for the vendor-provided and diagnostic setup, respectively. All differences were significant (p > 0.05). Image quality of our novel setup was judged suitable for contouring by expert-based assessment. Motion artifacts were found in 8/60 patients in the diagnostic setup, whereas none were found for patients in the RT setup. Site-specific core protocols were designed to minimize distortions while optimizing tissue contrast and 3D resolution according to indication-specific objectives. Conclusion: We present a novel setup for high-quality imaging in treatment position that allows use of several immobilization systems enabling MR-only workflows, which could reduce unnecessary dose and registration inaccuracies.
CRIS-Team Scopus Importer:2020-10-30
Keywords: Immobilization; MR-only treatment planning; Prostate; Simulation; Stereotactic radiosurgery

Implementation of machine learning into clinical breast MRI: Potential for objective and accurate decision-making in suspicious breast masses - Ellmann, Stephan; Wenkel, Evelyn; Dietzel, Matthias; Bielowski, Christian; Vesal, Sulaiman; Maier, Andreas; Hammon, Matthias; Janka, Rolf Matthias; Fasching, Peter; Beckmann, Matthias; Schulz-Wendtland, Rüdiger; Uder, Michael; et al. (PLoS ONE, 2020)
We investigated whether the integration of machine learning (ML) into MRI interpretation can provide accurate decision rules for the management of suspicious breast masses. A total of 173 consecutive patients with suspicious breast masses upon complementary assessment (BI-RADS IV/V: n = 100/76) received standardized breast MRI prior to histological verification. MRI findings were independently assessed by two observers (R1/R2: 5 years of experience/no experience in breast MRI) using six (semi-)quantitative imaging parameters. Interobserver variability was studied by ICC (intraclass correlation coefficient). A polynomial kernel function support vector machine was trained to differentiate between benign and malignant lesions based on the six imaging parameters and patient age. Ten-fold cross-validation was applied to prevent overfitting. Overall diagnostic accuracy and decision rules (rule-out criteria) to accurately exclude malignancy were evaluated. Results were integrated into a web application and published online. Malignant lesions were present in 107 patients (60.8%). Imaging features showed excellent interobserver variability (ICC: 0.81–0.98) with variable diagnostic accuracy (AUC: 0.65–0.82). Overall performance of the ML algorithm was high (AUC = 90.1%; BI-RADS IV: AUC = 91.6%). The ML algorithm provided decision rules to accurately rule-out malignancy with a false negative rate <1% in 31.3% of the BI-RADS IV cases. Thus, integration of ML into MRI interpretation can provide objective and accurate decision rules for the management of suspicious breast masses, and could help to reduce the number of potentially unnecessary biopsies.<br

Improved Visualization of Prostate Cancer Using Multichannel Computed Diffusion Images: Combining ADC and DWI - Hammon, Matthias; Saake, Marc; Laun, Frederik Bernd; Heiß, Rafael; Seuss, Nicola; Janka, Rolf Matthias; Cavallaro, Alexander Josef; Uder, Michael; Seuß, Hannes (Diagnostics, 2022)
(1) Background: For the peripheral zone of the prostate, diffusion weighted imaging (DWI) is the most important MRI technique; however, a high b-value image (hbDWI) must always be evaluated in conjunction with an apparent diffusion coefficient (ADC) map. We aimed to unify the important contrast features of both a hbDWI and ADC in one single image, termed multichannel computed diffusion images (mcDI), and evaluate the values of these images in a retrospective clinical study; (2) Methods: Based on the 2D histograms of hbDWI and ADC images of 70 patients with histologically proven prostate cancer (PCa) in the peripheral zone, an algorithm was designed to generate the mcDI. Then, three radiologists evaluated the data of 56 other patients twice in three settings (T2w images +): (1) hbDWI and ADC; (2) mcDI; and (3) mcDI, hbDWI, and ADC. The sensitivity, specificity, and inter-reader variability were evaluated; (3) Results: The overall sensitivity/specificity were 0.91/0.78 (hbDWI + ADC), 0.85/0.88 (mcDI), and 0.97/0.88 (mcDI + hbDWI + ADC). The kappa-values for the inter-reader variability were 0.732 (hbDWI + ADC), 0.800 (mcDI), and 0.853 (mcDI + hbDWI + ADC). (4) Conclusions: By using mcDI, the specificity of the MRI detection of PCa was increased at the expense of the sensitivity. By combining the conventional diffusion data with the mcDI data, both the sensitivity and specificity were improved.
CRIS-Team WoS Importer:2022-08-12

Improving diagnostic accuracy in assessing pulmonary edema on bedside chest radiographs using a standardized scoring approach - Hammon, Matthias; Dankerl, Peter; Voit-Hoehne, Heinz Leonhard; Sandmair, Martin; Kammerer, Ferdinand Josef; Uder, Michael; Janka, Rolf Matthias (BMC Anesthesiology, 2014)
To assess the value of a score-based system which allows standardized evaluation of pulmonary edema on bedside chest radiographs (CXRs) under routine clinical conditions.Seven experienced readers assessed bedside CXRs of ten patients with an extravascular lung water (EVLW)-value of <= 8 mL/kg (range: 4-8 mL/kg; indicates no pulmonary edema) and a series of ten patients with an EVLW-value of >= 15 mL/kg (range: 15-21 mL/kg; = indicates a pulmonary edema) with and without customized software which would permit a standardized assessment of the various indications of pulmonary edema. The software provides a score that identifies patients with and without pulmonary edema. EVLW-values were measured instantly after bedside CXR imaging using a pulse contour cardiac output (PiCCO) system and served as a reference standard. The patients were non-traumatic and not treated with diuretics or dobutamine during bedside CXR imaging and the PiCCO measurements. Mean sensitivity, specificity, positive and negative predictive value, the percentage of overall agreement and the free-marginal multirater kappa value was calculated for both the standard and the standardized score-based approach. The net reclassification index was calculated for each reader as well as for all readers.Evaluation of bedside CXRs by means of the score-based approach took longer (23 ± 12 seconds versus 7 ± 3 seconds without the use of the software) but improved radiologists' sensitivity (from 57 to 77%), specificity (from 90 to 100%) and the free-marginal multirater kappa value (from 0.34 to 0.68). The positive predictive value was raised from 85 to 100% and the negative predictive value from 68 to 81%. A net reclassification index of 0.3 (all readers) demonstrates an improvement in prediction performance gained by the score-based approach. The percentage of overall agreement was 67% with the standard approach and 84% with the software-based approach.The diagnostic accuracy of bedside CXRs to discriminate patients with elevated EVLW-values from those with a normal value can be improved with the use of a standardized score-based approach. The investigated system is freely available as a web-based application (accessible via: http://www.radiologie.uk-erlangen.de/aerzte-und-zuweiser/edema).
EVALuna2:14366

Interobserver and intermodality agreement of standardized algorithms for non-invasive diagnosis of hepatocellular carcinoma in high-risk patients: CEUS-LI-RADS versus MRI-LI-RADS - Schellhaas, Barbara; Hammon, Matthias; Strobel, Deike; Pfeifer, Lukas; Kielisch, Christian; Görtz, Rüdiger; Janka, Rolf Matthias; Neurath, Markus; Uder, Michael; Seuß, Hannes; Cavallaro, Alexander Josef (European Radiology, 2018)
OBJECTIVES: We compared the interobserver agreement for the recently introduced contrast-enhanced ultrasound (CEUS)-based algorithm CEUS-LI-RADS (Liver Imaging Reporting and Data System) versus the well-established magnetic resonance imaging (MRI)-LI-RADS for non-invasive diagnosis of hepatocellular carcinoma (HCC) in high-risk patients. METHODS: Focal liver lesions in 50 high-risk patients (mean age 66.2 ± 11.8 years; 39 male) were assessed retrospectively with CEUS and MRI. Two independent observers reviewed CEUS and MRI examinations, separately, classifying observations according to CEUS-LI-RADSv.2016 and MRI-LI-RADSv.2014. Interobserver agreement was assessed with Cohen's kappa. RESULTS: Forty-three lesions were HCCs; two were intrahepatic cholangiocarcinomas; five were benign lesions. Arterial phase hyperenhancement was perceived less frequently with CEUS than with MRI (37/50 / 38/50 lesions = 74%/78% [CEUS; observer 1/observer 2] versus 46/50 / 44/50 lesions = 92%/88% [MRI; observer 1/observer 2]). Washout appearance was observed in 34/50 / 20/50 lesions = 68%/40% with CEUS and 31/50 / 31/50 lesions = 62%/62%) with MRI. Interobserver agreement was moderate for arterial hyperenhancement (ĸ = 0.511/0.565 [CEUS/MRI]) and "washout" (ĸ = 0.490/0.582 [CEUS/MRI]), fair for CEUS-LI-RADS category (ĸ = 0.309) and substantial for MRI-LI-RADS category (ĸ = 0.609). Intermodality agreement was fair for arterial hyperenhancement (ĸ = 0.329), slight to fair for "washout" (ĸ = 0.202) and LI-RADS category (ĸ = 0.218) CONCLUSION: Interobserver agreement is substantial for MRI-LI-RADS and only fair for CEUS-LI-RADS. This is mostly because interobserver agreement in the perception of washout appearance is better in MRI than in CEUS. Further refinement of the LI-RADS algorithms and increasing education and practice may be necessary to improve the concordance between CEUS and MRI for the final LI-RADS categorization. KEY POINTS: • CEUS-LI-RADS and MRI-LIRADS enable standardized non-invasive diagnosis of HCC in high-risk patients. • With CEUS, interobserver agreement is better for arterial hyperenhancement than for "washout". • Interobserver agreement for major features is moderate for both CEUS and MRI. • Interobserver agreement for LI-RADS category is substantial for MRI, and fair for CEUS. • Interobserver-agreement for CEUS-LI-RADS will presumably improve with ongoing use of the algorithm.
EVALuna2:34689

Kommentar zu „MSK - Diffusions-Mikrostrukturbildgebung der Schulter - Janka, Rolf Matthias (Röfo: Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2023)
CRIS-Team Scopus Importer:2023-11-24

Left Ventricular Structure in Patients With Mild-to-Moderate CKD-a Magnetic Resonance Imaging Study - Schneider, Markus; Scheppach, Johannes B.; Raff, Ulrike; Toncar, Sebastian; Ritter, Christian; Klink, Thorsten; Stoerk, Stefan; Wanner, Christoph; Schlieper, Georg; Saritas, Turgay; Reinartz, Sebastian D.; Floege, Juergen; et al. (Kidney International Reports, 2019)
Introduction: The high burden of left ventricular (LV) abnormalities in patients with advanced chronic kidney disease (CKD) is well established. However, less is known about the prevalence, patterns, and determinants of LV abnormalities in patients with early CKD.
CRIS-Team WoS Importer:2019-02-21

Machine Learning-Supported Diagnosis of Small Blue Round Cell Sarcomas Using Targeted RNA Sequencing. - Schlieben, Lea D.; Carta, Maria Giulia; Moskalev, Evgeny; Stöhr, Robert; Metzler, Markus; Besendörfer, Manuel; Meidenbauer, Norbert; Semrau, Sabine; Janka, Rolf Matthias; Grützmann, Robert; Wiemann, Stefan; Hartmann, Arndt; et al. (Journal of Molecular Diagnostics, 2024)
Small blue round cell sarcomas (SBRCSs) are a heterogeneous group of tumors with overlapping morphologic features but markedly varying prognosis. They are characterized by distinct chromosomal alterations, particularly rearrangements leading to gene fusions, whose detection currently represents the most reliable diagnostic marker. Ewing sarcomas are the most common SBRCSs, defined by gene fusions involving EWSR1 and transcription factors of the ETS family, and the most frequent non-EWSR1-rearranged SBRCSs harbor a CIC rearrangement. Unfortunately, currently the identification of CIC::DUX4 translocation events, the most common CIC rearrangement, is challenging. Here, we present a machine-learning approach to support SBRCS diagnosis that relies on gene expression profiles measured via targeted sequencing. The analyses on a curated cohort of 69 soft-tissue tumors showed markedly distinct expression patterns for SBRCS subgroups. A random forest classifier trained on Ewing sarcoma and CIC-rearranged cases predicted probabilities of being CIC-rearranged >0.9 for CIC-rearranged-like sarcomas and <0.6 for other SBRCSs. Testing on a retrospective cohort of 1335 routine diagnostic cases identified 15 candidate CIC-rearranged tumors with a probability >0.75, all of which were supported by expert histopathologic reassessment. Furthermore, the multigene random forest classifier appeared advantageous over using high ETV4 expression alone, previously proposed as a surrogate to identify CIC rearrangement. Taken together, the expression-based classifier can offer valuable support for SBRCS pathologic diagnosis.
EVALuna2:565265

Magnetic resonance cinematography of the fingers: a 3.0 Tesla feasibility study with comparison of incremental and continuous dynamic protocols - Bayer, Thomas; Adler, Werner; Janka, Rolf Matthias; Uder, Michael; Roemer, Frank (Skeletal Radiology, 2017)
To study the feasibility of magnetic resonance cinematography of the fingers (MRCF) with comparison of image quality of different protocols for depicting the finger anatomy during motion.MRCF was performed during a full flexion and extension movement in 14 healthy volunteers using a finger-gating device. Three real-time sequences (frame rates 17-59 images/min) and one proton density (PD) sequence (3 images/min) were acquired during incremental and continuous motion. Analyses were performed independently by three readers. Qualitative image analysis included Likert-scale grading from 0 (useless) to 5 (excellent) and specific visual analog scale (VAS) grading from 0 (insufficient) to 100 (excellent). Signal-to-noise calculation was performed. Overall percentage agreement and mean absolute disagreement were calculated.Within the real-time sequences a high frame-rate true fast imaging with steady-state free precession (TRUFI) yielded the best image quality with Likert and overall VAS scores of 3.0 ± 0.2 and 60.4 ± 25.3, respectively. The best sequence regarding image quality was an incremental PD with mean values of 4.8 ± 0.2 and 91.2 ± 9.4, respectively. Overall percentage agreement and mean absolute disagreement were 47.9 and 0.7, respectively. No statistically significant SNR differences were found between continuous and incremental motion for the real-time protocols.MRCF is feasible with appropriate image quality during continuous motion using a finger-gating device. Almost perfect image quality is achievable with incremental PD imaging, which represents a compromise for MRCF with the drawback of prolonged scanning time.
EVALuna2:14720

Magnetic resonance imaging for brain stereotactic radiotherapy - A review of requirements and pitfalls - Putz, Florian; Mengling, Veit; Perrin, Rosalind; Masitho, Siti; Weissmann, Thomas; Roesch, Johannes; Bäuerle, Tobias; Janka, Rolf Matthias; Uder, Michael; Amarteifio, Patrick; Doussin, Sylvain; Schmidt, Manuel; et al. (Strahlentherapie und Onkologie, 2020)
Due to its superior soft tissue contrast, magnetic resonance imaging (MRI) is essential for many radiotherapy treatment indications. This is especially true for treatment planning in intracranial tumors, where MRI has a long-standing history for target delineation in clinical practice. Despite its routine use, care has to be taken when selecting and acquiring MRI studies for the purpose of radiotherapy treatment planning. Requirements on MRI are particularly demanding for intracranial stereotactic radiotherapy, where accurate imaging has a critical role in treatment success. However, MR images acquired for routine radiological assessment are frequently unsuitable for high-precision stereotactic radiotherapy as the requirements for imaging are significantly different for radiotherapy planning and diagnostic radiology. To assure that optimal imaging is used for treatment planning, the radiation oncologist needs proper knowledge of the most important requirements concerning the use of MRI in brain stereotactic radiotherapy. In the present review, we summarize and discuss the most relevant issues when using MR images for target volume delineation in intracranial stereotactic radiotherapy.
CRIS-Team WoS Importer:2020-04-10

Measurement of kidney perfusion by magnetic resonance imaging: Comparison of MRI with arterial spin labeling to para-aminohippuric acid plasma clearance in male subjects with metabolic syndrome - Ritt, Martin; Janka, Rolf Matthias; Schneider, Markus P.; Martirosian, Petros; Hornegger, Joachim; Bautz, Werner; Uder, Michael; Schmieder, Roland (Nephrology Dialysis Transplantation, 2010)
Background. Magnetic resonance imaging with arterial spin labeling (MRI-ASL) is a non-invasive approach to measure organ perfusion. We aimed to examine whether MRI-ASL kidney perfusion measurements are related to measurements of renal plasma flow (RPF) by para-aminohippuric acid (PAH) plasma clearance and whether changes of kidney perfusion in response to treatment with telmisartan can be detected by MRI-ASL.Methods. Twenty-four patients with metabolic syndrome and an estimated creatinine clearance according to Cockroft and Gault of ≥60ml/min were included in the study. Kidney perfusion was assessed by MRI-ASL measurements of a single coronal kidney slice (with flow-sensitive alternating inversion recovery and true fast imaging with steady-state processing sequence) and by measurements of RPF using PAH plasma clearance before and after 2 weeks of treatment with the angiotensin receptor blocker telmisartan. All MRI-ASL examinations were performed on a 1.5 T scanner.Results. Two weeks of therapy with telmisartan led to a significant increase of RPF (from 313 ± 47 to 348 ± 69ml/min/m, P = 0.007) and MRI-ASL kidney perfusion measurements (from 253 ± 20 to 268 ± 25ml/min/100g, P = 0.020). RPF measurements were related with MRI-ASL kidney perfusion measurements (r = 0.575, P < 0.001). Changes of RPF measurements and changes of MRI-ASL kidney perfusion measurements in response to treatment with telmisartan revealed a close relationship when expressed in absolute terms (r = 0.548, P = 0.015) and in percentage changes (r = 0.514, P = 0.025).Conclusions. Perfusion measurement of a single coronal kidney slice by MRI-ASL is able to approximate kidney perfusion and to approximate changes in kidney perfusion due to pharmacological intervention. © 2009 The Author.

Mid-Term Vascular Safety of Renal Denervation Assessed by Follow-up MR Imaging. - Schmid, Axel; Schmieder, Raphael; Lell, Michael; Janka, Rolf Matthias; Veelken, Roland; Schmieder, Roland; Uder, Michael; Ott, Christian (Cardiovascular and Interventional Radiology, 2016)
Renal denervation (RDN) emerged as a treatment option for reducing blood pressure (BP) in patients with treatment-resistant hypertension (TRH). However, concerns have been raised regarding the incidence of late renal artery stenosis or thromboembolism after RDN. The goal of the current study was, therefore, to conduct a prospective clinical trial on the mid-term vascular integrity of the renal arteries and the perfusion of the renal parenchyma assessed by magnetic resonance imaging (MRI) in the follow-up after catheter-based RDN.In our single-centre investigator initiated study, 51 patients with true TRH underwent catheter-based RDN using the Symplicity Flex(TM) catheter (Medtronic Inc., Palo Alto, CA). Follow-up MRI was performed at a median of 11 months (interquartile range 6-18 months) after RDN on a 1.5T MR unit. High-resolution MR angiography (MRA) and MRI results were compared to the baseline digital angiography of renal arteries obtained at time of RDN. In case of uncertainties (N = 2) catheter angiography was repeated.Both office and 24-h ambulatory BP were significantly reduced 6 and 12 months after RDN. Renal function remained unchanged 6 and 12 months after RDN. In all patients, MRA excluded new or progression of pre-existing low grade renal artery stenosis as well as focal aneurysms at the sites of radiofrequency ablation. In none of the patients new segmental perfusion deficits in either kidney were detected on MRI.No vascular or parenchymal complications after radiofrequency-based RDN were detected in 51 patients followed up by MRI.
EVALuna2:3794

Model-based pancreas segmentation in portal venous phase contrast-enhanced CT images - Hammon, Matthias; Cavallaro, Alexander Josef; Erdt, Marius; Dankerl, Peter; Kirschner, Matthias; Drechsler, Klaus; Wesarg, Stefan; Uder, Michael; Janka, Rolf Matthias (Journal of Digital Imaging, 2013)
This study aims to automatically detect and segment the pancreas in portal venous phase contrast-enhanced computed tomography (CT) images. The institutional review board of the University of Erlangen-Nuremberg approved this study and waived the need for informed consent. Discriminative learning is used to build a pancreas tissue classifier incorporating spatial relationships between the pancreas and surrounding organs and vessels. Furthermore, discrete cosine and wavelet transforms are used to build texture features to describe local tissue appearance. Classification is used to guide a constrained statistical shape model to fit the data. The algorithm to detect and segment the pancreas was evaluated on 40 consecutive CT data that were acquired in the portal venous contrast agent phase. Manual segmentation of the pancreas was carried out by experienced radiologists and served as reference standard. Threefold cross validation was performed. The algorithm-based detection and segmentation yielded an average surface distance of 1.7 mm and an average overlap of 61.2 % compared with the reference standard. The overall runtime of the system was 20.4 min. The presented novel approach enables automatic pancreas segmentation in portal venous phase contrast-enhanced CT images which are included in almost every clinical routine abdominal CT examination. Reliable pancreatic segmentation is crucial for computer-aided detection systems and an organ-specific decision support. © 2013 The Author(s).
CRIS-Team Scopus Importer:2023-03-08
Keywords: Computed tomography; Computer-assisted detection; Machine learning; Pancreas; Segmentation

Modern low-field MRI - Pogarell, Tobias; Heiß, Rafael; Janka, Rolf Matthias; Nagel, Armin Michael; Uder, Michael; Roemer, Frank (Skeletal Radiology, 2024)
This narrative review explores recent advancements and applications of modern low-field (≤ 1 Tesla) magnetic resonance imaging (MRI) in musculoskeletal radiology. Historically, high-field MRI systems (1.5 T and 3 T) have been the standard in clinical practice due to superior image resolution and signal-to-noise ratio. However, recent technological advancements in low-field MRI offer promising avenues for musculoskeletal imaging. General principles of low-field MRI systems are being introduced, highlighting their strengths and limitations compared to high-field counterparts. Emphasis is placed on advancements in hardware design, including novel magnet configurations, gradient systems, and radiofrequency coils, which have improved image quality and reduced susceptibility artifacts particularly in musculoskeletal imaging. Different clinical applications of modern low-field MRI in musculoskeletal radiology are being discussed. The diagnostic performance of low-field MRI in diagnosing various musculoskeletal pathologies, such as ligament and tendon injuries, osteoarthritis, and cartilage lesions, is being presented. Moreover, the discussion encompasses the cost-effectiveness and accessibility of low-field MRI systems, making them viable options for imaging centers with limited resources or specific patient populations. From a scientific standpoint, the amount of available data regarding musculoskeletal imaging at low-field strengths is limited and often several decades old. This review will give an insight to the existing literature and summarize our own experiences with a modern low-field MRI system over the last 3 years. In conclusion, the narrative review highlights the potential clinical utility, challenges, and future directions of modern low-field MRI, offering valuable insights for radiologists and healthcare professionals seeking to leverage these advancements in their practice.
CRIS-Team Scopus Importer:2024-03-01
Keywords: 0.55 Tesla; Field strength; Joints; Knee; Low-field; MRI; Musculoskeletal radiology

MRI as a Stressor: The Psychological and Physiological Response of Patients to MRI, Influencing Factors, and Consequences - Madl, Janika; Janka, Rolf Matthias; Bay, Susanne; Rohleder, Nicolas (JACR Journal of the American College of Radiology, 2022)
Objective: Despite being noninvasive and painless, MRI is recurrently associated with stress and anxiety in patients. This adversely affects patient experience and may be associated with negative outcomes for the health care provider. This study examined the psychological and physiological response of patients to MRI and how these response levels relate, the role of different potentially influencing factors, and the relation to procedural outcomes. Methods: Data of 96 patients (mean 48.77 ± 15.11 years; 61.5% female) were included. The patients’ psychological or physiological response was assessed before and after MRI via questionnaires on anxiety, strain, agitation, and mood and salivary α-amylase, and cortisol. Data on potentially influencing factors and outcomes of the clinical workflow were collected via questionnaires. Results: We observed significant improvements of all psychological measures from pre- to post-MRI (all P < .001) but not of the physiological stress markers (all P > .258). The psychological response correlated with levels of cortisol but not α-amylase. The valence of previous MRI experiences was particularly predictive of the patients’ reaction. Stress and anxiety in patients significantly predicted the probability of scan repetitions (Nagelkerke's R2 = .31, P = .011) and scan duration (adjusted R2 = .22, P < .001). Conclusion: These findings imply that various factors contribute to the patients’ response to MRI. Stress and anxiety in patients, in turn, may impact the clinical workflow. Therefore, these factors should be considered in the medical treatment to provide both a positive patient experience and smooth clinical workflows.
CRIS-Team Scopus Importer:2022-02-25
Keywords: Anxiety; MRI; patient experience; physiological stress response; unexpected patient-related events

MRI Diagnostics of the Fingers: Current Developments and Clinical Relevance MRT-Diagnostik der Finger aktuelle Entwicklungen und klinische Relevanz - Bayer, Thomas; Lutter, Christoph; Janka, Rolf Matthias; Uder, Michael; Roemer, Frank (Röfo: Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2025)
Background Magnetic resonance imaging (MRI) is an excellent method for visualizing the complex anatomical structures of the fingers. The high diagnostic standard is based on numerous recent technical developments to improve soft tissue differentiation and detail recognition, and includes time-resolved functional imaging Method This review highlights the current status of MRI in finger diagnostics. The content of this narrative review is based on a literature search in the PubMed and Google Scholar databases using the search terms finger MRI and finger imaging. Conclusion Due to numerous technical optimizations and the increasing clinical availability of MRI, this examination has become indispensable in routine use for the further clarification of traumatic and orthopedic clinical pictures. MRI is also playing an increasingly important role in rheumatic and inflammatory issues, as well as tumors, whereby the particularly high potential for early detection and the detailed soft tissue imaging are especially advantageous. Key Points MRI enables precise differential diagnosis of all clinical pictures of the fingers and is useful in the clarification of traumatic, orthopedic, rheumatic, inflammatory, and neoplastic issues. Multi-channel hand coils, scanners with high magnetic field strengths, and the use of contrast agents have led to an evaluation with resolutions in the submillimeter range in some cases. High-resolution MRI, including the possibility of functional examination, makes it easier to determine adequate therapy and avoid subsequent damage while meeting high standards. Citation Format Bayer T, Lutter C, Janka R et al.
CRIS-Team Scopus Importer:2025-06-06
Keywords: finger; inflammation; MRI; trauma; tumor

Mri of finger pulleys at 7t—direct characterization of pulley ruptures in an ex vivo model - Heiß, Rafael; Librimir, Alexander; Lutter, Christoph; Janka, Rolf Matthias; Kuerten, Stefanie; Roemer, Frank; Nagel, Armin Michael; Uder, Michael; Bayer, Thomas (Diagnostics, 2021)
The aim of this study was to evaluate 7 Tesla (7T) magnetic resonance imaging (MRI) for direct visualization and specific characterization of the finger flexor pulleys A2, A3, and A4 before and after ex vivo pulley rupture. Thirty fingers of human cadavers were examined before and after pulley disruption with a 26 min clinical 7T pulse sequence protocol. Images were assessed by two experienced radiologists for the presence of pulley rupture. Injury characterization included definition of rupture location, morphology, and complications. Image quality was evaluated according to a 4-point Likert-type scale from “not evaluable” to “excellent”. Macroscopic preparations were used as the reference standard. Direct characterization of intact A2, A3, and A4 pulleys and the corresponding pulley lesions was possible in all cases. The rupture location was distributed equally at the radial, ulnar, and central parts of the pulleys. A dislocation and intercalation of the pulley stump between the flexor tendon and finger phalanges was observed as a complication in 62.5% of cases. The average Likert score for direct visualization of pulleys was 2.67 before rupture and 2.79 after rupture creation, demonstrating adequate image quality for routine application. 7T MRI enables a direct characterization of A2, A3, and A4 pulleys before and after artificial disruption, including the definition of rupture morphology and location as well as the detection of rupture complications. This promises a precise presurgical evaluation of pulley injuries and complicated pulley stump dislocations.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Climbing; Finger flexor pulleys; Imaging; Injury classification; Ultra-high-field MRI

MyCases-a portable application for radiologic case collections - Kammerer, Ferdinand Josef; Janka, Rolf Matthias; Kramer, Manuel; Hammon, Matthias; Uder, Michael; Schlechtweg, Philipp (Journal of Digital Imaging, 2014)
Radiologists come across interesting patient cases almost every day. This work proposes a novel case database server for quick and easy storage of such cases including whole image series, patient data, and annotations. Cases can be added to the database by saving DICOM images into a predefined directory on the local network. The application automatically extracts patient and study data from the DICOM header and saves it in the database while images are stored as anonymized JPEG files. Users can mark their cases as private or public (visible to all users). Different data fields for annotations and categorization of a case are available. The user frontend also provides several retrieval mechanisms allowing for browsing the cases and performing different kinds of search queries. The stored series can be scrolled interactively in the form of scrollable image stacks. The project is realized as a web-based application using a portable web and database server software package (XAMPP). This makes the system very lightweight and easy to run on almost any desktop computer, even from a USB flash drive, without the need for deeper IT knowledge and administrative rights.
EVALuna2:14373

Numerical investigation of the hydrodynamics of changing fin positions within a 4-fin surfboard configuration - Falk, Sebastian; Kniesburges, Stefan; Janka, Rolf Matthias; O'Keefe, Tom; Grosso, Roberto; Döllinger, Michael (Applied Sciences, 2020)
Most sports like surfing are highly developed. It is necessary to tease the last percentages out of the competitors and equipment-in the case of surfing the surfboard-fin-system-to win competitions or championships. In this computational investigation, a parameter study of the positioning of the two rear fins within a 4-fin configuration with fixed front fins on a surfboard is executed to find appropriate fin positions for specific surf situations. Four different inflow velocities are investigated. The RANS and URANS models combined with the SST k-ω turbulence model, which is available within the computational fluid dynamics (CFD) package STAR-CCM+, are used to simulate the flow field around the fins for angles of attack (AoA) between 0° and 45°. The simulation results show that shifting the rear fins toward the longitudinal axis of the surfboard lowers the maximum lift. Surfboards with 4-fin configurations are slower in nearly the whole range of AoA due to a higher drag force but produce a higher lift force compared to the 3-fin configuration. The lift and drag forces increase significantly with increasing inflow velocity. This study shows a significant influence of the rear fin positioning and the inflow velocity on lift and drag performance characteristics.
CRIS-Team Scopus Importer:2020-03-27
Keywords: Computational fluid dynamics (CFD); Fins; Hydrodynamics; Quad; STAR-CCM+®; Surfboard

Osteitis and synovitis, but not bone erosion, is associated with proteoglycan loss and microstructure damage in the cartilage of patients with rheumatoid arthritis - Herz, Barbara; Albrecht, Andreas; Englbrecht, Matthias; Welsch, Götz; Uder, Michael; Renner, Nina; Schlechtweg, Philipp; Paul, Dominik; Lauer, Lars; Engelke, Klaus; Janka, Rolf Matthias; Rech, Jürgen; et al. (Annals of the Rheumatic Diseases, 2014)
To investigate the relation between anatomic changes of the synovium, the bone, the bone marrow and the cartilage to biochemical properties of the cartilage in patients with rheumatoid arthritis (RA).33 patients with RA received 3-T MRI scans of the metacarpophalangeal joints. Two independent methods, (A) the delayed gadolinium enhanced MRI of the cartilage (dGEMRIC, T2-mapping), which was used to assess the biochemical properties of the cartilage; (B) synovitis, osteitis and bone erosions were quantified according to the RA MRI scoring (RAMRIS) method and cartilage thickness (CT), interbone joint space (IBJS, distance between proximal and distal bone surface) and intercartilage joint space (ICJS, distance between proximal and distal cartilage surface) were measured.Biochemical changes of the cartilage, corresponding to low dGEMRIC and high T2 values, were more likely to be seen in joints with decreased IBJS and ICJS as well as decreased CT. For instance, dGEMRIC was directly correlated to the IBJS (p=0.001) and ICJS (p=0.001), whereas T2 mapping was inversely correlated to IBJS and ICJS (both p=0.017). Moreover, the degree of osteitis, and to some extent synovitis, was correlated to biochemical cartilage changes as measured by dGEMRIC (p=0.003) or the T2 mapping (p=0.013). By contrast, bone erosions did not correlate to the degree of biochemical cartilage changes.These data support the concept that synovitis and osteitis may be two main triggers for cartilage damage. Thus, the actual inflammatory state of a joint, but not so much the degree of bone erosion, appears to influence cartilage properties in RA.
EVALuna2:10039

Paragangliomas of the Head and Neck: Local Control and Functional Outcome Following Fractionated Stereotactic Radiotherapy - Weissmann, Thomas; Lettmaier, Sebastian; Roesch, Johannes; Mengling, Veit; Bert, Christoph; Iro, Heinrich; Hornung, Joachim; Janka, Rolf Matthias; Semrau, Sabine; Fietkau, Rainer; Putz, Florian (American Journal of Clinical Oncology-Cancer Clinical Trials, 2019)
Objectives: To investigate local control and functional outcome following state-of-the-art fractionated stereotactic radiotherapy (FSRT) for paragangliomas of the head and neck. Methods: In total, 40 consecutive patients with paragangliomas of the head and neck received conventionally FSRT from 2003 to 2016 at the Department of Radiation Oncology of the University Hospital Erlangen. Local control, toxicities, and functional outcome were examined during follow-up. In total, 148 magnetic resonance imaging studies were subjected to longitudinal volumetric analysis using whole tumor segmentation in a subset of 22 patients. Results: A total of 80.0% (32/40) of patients received radiotherapy as part of their primary treatment. In 20.0% (8/40) of patients, radiation was used as salvage treatment after tumor recurrence in patients initially treated with surgery alone. The median dose applied was 54.0 Gy (interdecile range, 50.4 to 56.0 Gy) in single doses of 1.8 or 2 Gy. Local control was 100% after a median imaging follow-up of 52.2 months (range, 0.8 to 152.9 mo). The volumetric analysis confirmed sustained tumor control in a subset of 22 patients and showed transient enlargement (range, 129.6% to 151.2%) in 13.6% of cases (3/22). After a median volumetric follow-up of 24.6 months mean tumor volume had diminished to 86.1% compared with initial volume. In total, 52.5% (21/40) of patients reported improved symptoms after radiotherapy, 40% (16/40) observed no subjective change with only 7.5% (3/40) reporting significant worsening. Conclusions: State-of-the-art FSRT provides excellent control and favorable functional outcome in patients with paragangliomas of the head and neck. The volumetric analysis provides improved evidence for sustained tumor control.
CRIS-Team Scopus Importer:2019-10-22
Keywords: fractionated stereotactic radiotherapy; functional outcomes; paraganglioma; tumor control; volumetric analysis

Pediatric cardiac MRI: automated left-ventricular volumes and function analysis and effects of manual adjustments - Hammon, Matthias; Janka, Rolf Matthias; Dankerl, Peter; Glöckler, Martin; Kammerer, Ferdinand J.; Dittrich, Sven; Uder, Michael; Rompel, Oliver (Pediatric Radiology, 2015)
Cardiac MRI is an accurate and reproducible technique for the assessment of left ventricular volumes and function. The accuracy of automated segmentation and the effects of manual adjustments have not been determined in children.To evaluate automated segmentation and the effects of manual adjustments for left ventricular parameter quantification in pediatric cardiac MR images.Left ventricular parameters were evaluated in 45 children with suspected myocarditis (age 13.4 ± 3.5 years, range 4-17 years) who underwent cardiac MRI. Dedicated software was used to automatically segment and adjust the parameters. Results of end-diastolic volume, end-systolic volume, stroke volume, myocardial mass, and ejection fraction were documented before and after apex/base adjustment and after apex/base/myocardial contour adjustment.The software successfully detected the left ventricle in 42 of 45 (93.3%) children; failures occurred in the smallest and youngest children. Of those 42 children, automatically segmented end-diastolic volume (EDV) was 151 ± 47 ml, and after apex/base adjustment it was 146 ± 45 ml, after apex/base/myocardial contour adjustment 146 ± 45 ml. The corresponding results for end-systolic volume (ESV) were 66 ± 32 ml, 63 ± 29 ml and 64 ± 28 ml; for stroke volume (SV) they were 85 ± 25 ml, 83 ± 23 ml and 83 ± 23 ml; for ejection fracture (EF) they were 57 ± 10%, 58 ± 9% and 58 ± 9%, and for myocardial mass (MM) they were 104 ± 31 g, 95 ± 31 g and 94 ± 30 g. Statistically significant differences were found when comparing the EDV/ESV/MM results, the EF results after apex/base adjustment and after apex/base/myocardial contour adjustment and the SV results (except for comparing the SVs after apex/base adjustment and after apex/base/myocardial contour adjustment).Automated segmentation for the evaluation of left ventricular parameters in pediatric MR images proved to be feasible. Automated segmentation + apex/base adjustment provided clinically acceptable parameters for the majority of cases.
EVALuna2:14344

Pigmented villonodular synovitis. A rare differential diagnosis of synovial joint swelling - Jendrissek, Andreas; Hotfiel, Thilo; Swoboda, Bernd; Söder, Stephan; Janka, Rolf Matthias (Zeitschrift für Rheumatologie, 2016)
Pigmented villonodular synovitis (PVNS) describes a rare disease caused by an abnormal proliferation of the synovial membrane in large and small joints. In order to achieve an optimal result of treatment it is necessary to carry out specific diagnostics and a targeted therapy approach.This article gives a review of the epidemiology, etiopathogenesis and diagnostic management of PVNS as well as presenting the current therapy and treatment recommendations.A systematic search of the literature was performed in the databank of the National Center for Biotechnology Information ( http://www.ncbi.nlm.nih.gov/pubmed ). The search targeted randomized clinical and experimental studies, systematic and non-systematic review articles, expert opinions and case reports related to PVNS, independent of the level of evidence attained by each study.The differential diagnosis of PVNS should be considered in cases of recurrent hemorrhagic joint effusions. The cause of the disease has not yet been exactly clarified. The final diagnosis can ultimately only be confirmed by histological investigations. In order to obtain representative histological tissue samples for the diagnosis, magnetic resonance imaging (MRI) with the appropriate heme sequences should be carried out prior to taking samples. The management of PVNS is often difficult due to the high risk of recurrence depending on the various forms. In view of the high rate of recurrence, therapy should include a complete synovectomy.For the surgical approach arthroscopic and open procedures have been described, which are currently controversially discussed with respect to the complication and recurrence rates. Adjuvant interventional therapy forms, such as radiosynoviorthesis are recommended to reduce the recurrence rate.
EVALuna2:6817

PIK3CA mutation testing as a valuable molecular surrogate for lipomatosis of the median nerve: clinicopathological and molecular analysis of six cases - Osterloh, Justus; Agaimy, Abbas; Fried, Frederick; Stöhr, Robert; Janka, Rolf Matthias; Arkudas, Andreas; Horch, Raymund E. (Virchows Archiv, 2023)
Lipomatosis of peripheral nerves (LPN, also known as fibrolipomatous or lipofibromatous hamartoma of peripheral nerves) is a very rare, benign, intraneural, tumorous lesion that predominantly involves the median nerve but may rarely affect any peripheral nerve. Recently, PIK3CA mutations have been reported in macrodactyly, a rare condition related to LPN, and in other localized lipomatous overgrowth syndromes. In this retrospective study, we report 6 cases of FPN involving the median nerve (4 of them identified among 570 patients with carpal tunnel syndrome who underwent surgical decompression at our center from 2012 to 2022 and two seen in consultation by one of the authors). All cases were diagnosed via biopsy or resection supplemented by MRI. Patients were 4 males and 2 females aged 23 to 60 years (mean 38 years). One patient with bilateral lesions had in addition extensive angiomatosis of the paravertebral region. Histological examination showed an abnormal amount of mature fatty tissue containing disordered fibrous bands, entrapping normal-looking nerve fibers with prominent perineurial and endoneurial fibrosis. Genetic analysis using snapshot assay constructed to detect hotspots mutations in PIK3CA revealed similar PIK3CA mutations (p.H1047R; c.3140A>G) in 5/6 cases (83.3%). Our study represents a further contribution to the literature on LPN and highlights the diagnostic value of PIK3CA mutation testing as surrogate tool in equivocal cases and in those lesions without associated macrodactyly, especially as the biopsy findings of this lesion are essentially nonspecific.
CRIS-Team Scopus Importer:2023-04-28
Keywords: Everolimus; Lipomatosis; mTOR; Neuropathy; Peripheral nerves; Sequencing

Preparing patients according to their individual coping style improves patient experience of magnetic resonance imaging - Madl, Janika; Sturmbauer, Sarah; Janka, Rolf Matthias; Bay, Susanne; Rohleder, Nicolas (Journal of Behavioral Medicine, 2022)
MRI-related anxiety is present in 30% of patients and may evoke motion artifacts/failed scans, which impair clinical efficiency. It is unclear how patient anxiety can be countered most effectively. Habitual preferences for coping with stressful situations by focusing or distracting one's attention thereof (coping style) may play a key role in this context. This study aimed to compare the effectiveness of two patient-preparation videos with informational vs. relaxational content and to determine whether the fit between content and coping style affects effectivity. The sample consisted of 142 patients (M = 48.31 +/- 15.81 years). Key outcomes were anxiety, and cortisol as a physiological stress marker. When not considering coping style, neither intervention improved the patients' reaction; only patient preparation that matched the patients' coping style was associated with an earlier reduction of anxiety. This suggests that considering individual preferences for patient preparation may be more effective than a one-size-fits-all approach.
CRIS-Team WoS Importer:2022-09-16

Protocol Recommendations of the AG Imaging Procedures of the Musculoskeletal System (AG BVB) to Measurement Sequences for Finger, Foot and Temporomandibular Joint - Rehnitz, Christoph; Janka, Rolf Matthias (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2019)
CRIS-Team WoS Importer:2019-04-12

Protokollempfehlungen der AG Bildgebende Verfahren des Bewegungsapparats (AG BVB) zu Mess-Sequenzen für Finger, Fuß und Kiefergelenk - Rehnitz, Christoph; Janka, Rolf Matthias (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2019)
CRIS-Team Scopus Importer:2019-06-04

Quantitative T2 Mapping Shows Increased Degeneration in Adjacent Intervertebral Discs Following Kyphoplasty - Pachowsky, Milena; Kleyer, Arnd; Wagner, Lisa; Langenbach, Andreas; Simon, David; Janka, Rolf Matthias; May, Matthias; Welsch, Goetz H. (Cartilage, 2018)
Objective A minimally invasive treatment of osteoporotic and nonosteoporotic thoracic and lumbar spine fractures is cement augmentation (kyphoplasty). Little is known about the impact on adjacent intervertebral discs. A quantitative magnetic resonance imaging (MRI) approach in addition to morphological MRI is desirable to evaluate changes in the intervertebral disc. Our study aims to evaluate the feasibility of T2 mapping for the detection of subtle changes in the intervertebral discs in spines after kyphoplasty. Design Intervertebral discs were assessed by quantitative MRI (3.0 T) using T2 relaxation time mapping. Region of interest (ROI; 6 per disc) analyses were performed. The ROIs at the anterior and posterior edges were interpreted as annulus fibrosus (AF). The 2 very inner zones were regarded as nucleus pulposus (NP) and the regions in between as intermediate transition zone. We compared T2 relaxation time values of intervertebral discs adjacent to the vertebrae after kyphoplasty with those nonadjacent to vertebrae after kyphoplasty, especially in the NP. Results The analysis of the ROIs showed that the intervertebral discs of the adjacent vertebral segments are associated with reduced T2 values compared to those that are nonadjacent to the affected vertebrae. Conclusion This study is to our knowledge the first investigation of intervertebral discs after kyphoplasty by quantitative MRI. Quantitative T2 mapping shows increased degeneration in adjacent intervertebral discs following kyphoplasty. Besides its contribution to a broader knowledge of postoperative changes after kyphoplasty, our findings may help to improve differentiation between healthy and degenerated intervertebral discs using these techniques.
EVALuna2:212498

Recurrent shock and pulmonary edema due to acetazolamide medication after cataract surgery - Zimmermann, S.; Achenbach, Susanne; Wolf, M.; Janka, Rolf Matthias; Marwan, M.; Mahler, V. (Heart & Lung, 2014)
We report a patient with recurrent shock and transient non-cardiogenic pulmonary edema within a period of two months - every time occurring after cataract surgery and a single oral dose of standard post-operative medication with acetazolamide.Records of the intensive care unit, review of the literature.This case demonstrates a rare but severe side effect of acetazolamide. We also present a review of the literature to raise the awareness of health care providers for this special form of non-cardiogenic pulmonary edema.
EVALuna2:11868

Regions at Risk in the Knee Joint of Young Professional Soccer Players: Longitudinal Evaluation of Early Cartilage Degeneration by Quantitative T2 Mapping in 3 T MRI - Schenker, Hannah; Simon, David; Waldenmeier, Leonie; Evers, Christoph; Janka, Rolf Matthias; Welsch, Goetz H.; Pachowsky, Milena (Cartilage, 2020)
Purpose. The study aims to detect regions at risk for (pre-)osteoarthritis in the tibiofemoral joint of young professional soccer players by evaluating cartilage composition by T2 mapping in a 3 T magnetic resonance imaging setting. Methods. In this longitudinal study, 20 professional adolescent soccer players were included. Tibiofemoral cartilage was assessed by quantitative T2 mapping and T2 values were evaluated by regions of interest analysis. Statistical evaluation, using Wilcoxon signed-rank tests, was performed to compare global T2 values and subregional T2 values between a baseline and a follow-up investigation 4.3 years later. Based on the average of playing time (15 years) we divided the cohort in 2 groups and differences were evaluated. Results. When comparing baseline and follow-up, our findings showed statistically significant increases of the global medial tibial and femoral T2 values. The most noticeable results of the subregional T2 analysis were statistically significant increases in the medial posterior zones (deep femoral 36.1 vs. 39.5, P = 0.001; superficial femoral 57.0 vs. 62.4, P = 0.034; deep tibial 28.3 vs. 34.1, P = 0.009; superficial tibial 43.2 vs. 55.3, P = 0.002). Conclusion. The elevation of T2 values in the medial, especially medial posterior, compartment of the knee joint indicates that these regions are at risk for early cartilage degeneration already at the time of adolescence. The findings can help individualize and optimize training concepts and to be aware of the chronic stress on these vulnerable areas. Prevention programs should be established in young players to avoid further cartilage damage.
CRIS-Team Scopus Importer:2020-06-02
Keywords: adolescent; cartilage; MRI; sports; T2 mapping

Renal fibrosis is the common feature of autosomal dominant tubulointerstitial kidney diseases caused by mutations in mucin 1 or uromodulin - Ekici, Arif Bülent; Hackenbeck, Thomas; Moriniere, Vincent; Panness, Andrea; Büttner, Maike; Uebe, Steffen; Janka, Rolf Matthias; Wiesener, Antje; Hermann, Ingo; Grupp, Sina; Hornberger, Martin; Huber, Tobias B.; et al. (Kidney International, 2014)
For decades, ill-defined autosomal dominant renal diseases have been reported, which originate from tubular cells and lead to tubular atrophy and interstitial fibrosis. These diseases are clinically indistinguishable, but caused by mutations in at least four different genes: UMOD, HNF1B, REN, and, as recently described, MUC1. Affected family members show renal fibrosis in the biopsy and gradually declining renal function, with renal failure usually occurring between the third and sixth decade of life. Here we describe 10 families and define eligibility criteria to consider this type of inherited disease, as well as propose a practicable approach for diagnosis. In contrast to what the frequently used term 'Medullary Cystic Kidney Disease' implies, development of (medullary) cysts is neither an early nor a typical feature, as determined by MRI. In addition to Sanger and gene panel sequencing of the four genes, we established SNaPshot minisequencing for the predescribed cytosine duplication within a distinct repeat region of MUC1 causing a frameshift. A mutation was found in 7 of 9 families (3 in UMOD and 4 in MUC1), with one indeterminate (UMOD p.T62P). On the basis of clinical and pathological characteristics we propose the term 'Autosomal Dominant Tubulointerstitial Kidney Disease' as an improved terminology. This should enhance recognition and correct diagnosis of affected individuals, facilitate genetic counseling, and stimulate research into the underlying pathophysiology.
EVALuna2:3695

RENAL HEMODYNAMIC CHANGES AFTER RENAL DENERVATION - Schmieder, R. S.; Schmid, Axel; Janka, Rolf Matthias; Ditting, T.; Veelken, Roland; Uder, Michael; Schmieder, Roland; Ott, Christian (2016)
EVALuna2:34706

Reproducibility of Kidney Perfusion Measurements With Arterial Spin Labeling at 1.5 Tesla MRI Combined With Semiautomatic Segmentation for Differential Cortical and Medullary Assessment - Hammon, Matthias; Janka, Rolf Matthias; Siegl, Christian; Seuß, Hannes; Grosso, Roberto; Martirosian, Petros; Schmieder, Roland; Uder, Michael; Kistner, Iris (Medicine, 2016)
Magnetic resonance imaging with arterial spin labeling (ASL) is a noninvasive approach to measure organ perfusion. The purpose of this study was to evaluate the reproducibility of ASL kidney perfusion measurements with semiautomatic segmentation, which allows separate quantification of cortical and medullary perfusion.The right kidneys of 14 healthy volunteers were examined 6 times on 2 occasions (3 times at each occasion). There was a 10-minute pause between each examination and a 14-day interval between the 2 occasions. Cortical, medullary, and whole kidney parenchymal perfusion was determined with customized semiautomatic segmentation software. Coefficient of variances (CVs) and intraclass correlations (ICCs) were calculated.Mean whole, cortical, and medullary kidney perfusion was 307.26 ± 25.65, 337.10 ± 34.83, and 279.61 ± 26.73 mL/min/100 g, respectively. On session 1, mean perfusion for the whole kidney, cortex, and medulla was 307.08 ± 26.91, 336.79 ± 36.54, and 279.60 ± 27.81 mL/min/100 g, respectively, and on session 2, 307.45 ± 24.65, 337.41 ± 33.48, and 279.61 ± 25.94 mL/min/100 g, respectively (P > 0.05; R = 0.60/0.59/0.54). For whole, cortical, and medullary kidney perfusion, the total ICC/CV were 0.97/3.43 ± 0.86%, 0.97/4.19 ± 1.33%, and 0.96/4.12 ± 1.36%, respectively. Measurements did not differ significantly and showed a very good correlation (P > 0.05; R = 0.75/0.76/0.65).ASL kidney measurements combined with operator-independent semiautomatic segmentation revealed high correlation and low variance of cortical, medullary, and whole kidney perfusion.
EVALuna2:3854

Rückenschmerz: Aktuelle Entwicklungen und Leitlinien - Braunschweig, R.; Janka, Rolf Matthias; Spahn, G.; Tiemann, A. (Radiologe, 2019)
Pain in general and back pain in particular are associated with a variety of pathological, clinical, and sociocultural factors. There are numerous clinical and therapeutic treatment as well as imaging-options available and comprehensive knowledge is required to meet the individual clinical needs of those affected. This requires a high degree of interdisciplinary cooperation. In addition, back pain is covered differently by various numbers of insurance companies. Imaging methods, including the example of periradicular image-assisted interventions, are presented with regard to their indication and efficiency. The existing guidelines and evaluation recommendations with different structural and targeted approaches are discussed in addition to extensive legal aspects in the literature. In addition, the structured reports and the certificated curricula of the AG Bildgebende Verfahren des Bewegungsapparates (Working Group „Imaging Procedures of the Musculoskeletal System”) of the Deutsche Röntgengesellschaft (“German Society of Radiology”) are recommended for the quality assurance.
CRIS-Team Scopus Importer:2019-12-20
Keywords: Backache; Computed tomography; Magnetic resonance imaging; Quality assurance; Standards

Scanned versus Fused-Reconstructed Oblique MR-Images for Assessment of the Tibiofibular Syndesmosis-Diagnostic PerFormance and Reader Agreement - Seuß, Hannes; Hammon, Matthias; Roemer, Frank; Heiß, Rafael; Janka, Rolf Matthias; Uder, Michael; Dankerl, Peter (Diagnostics, 2021)
To evaluate the diagnostic performance and reader agreement of a novel MRI image fusion method enabling the reconstruction of oblique images for the assessment of the tibiofibular syndesmosis. We evaluated 40 magnetic resonance imaging examinations of patients with ankle sprains (16 with ruptures and 24 without) for the presence of anteroinferior tibiofibular ligament rupture. For all patients, we performed a fusion of standard two-dimensional transversal and coronal 3 mm PDw TSE images into an oblique-fusion reconstruction (OFR) and compared these against conventionally scanned oblique sequence for the evaluation of the tibiofibular syndesmosis. To evaluate diagnostic performance, two expert readers independently read the OFR images twice. We analyzed sensitivity, specificity, negative and positive predictive values, accuracy, and agreement. Reader 1 misinterpreted one OFR as a false negative, demonstrating a sensitivity of 0.94 and specificity of 1.00, reader 2 demonstrated perfect accuracy. Intrareader agreement was almost perfect for reader 1 (alpha = 0.95) and was perfect for reader 2 (alpha = 1.00). Additionally, interreader agreement between all fusion sequence reads was almost perfect (alpha = 0.97). The proposed OFR enables reliable detection of anteroinferior tibiofibular ligament rupture with excellent inter- and intrareader agreement, making conventional scanning of oblique images redundant and supplies a method to retroactively create oblique images, e.g., from external examinations.
CRIS-Team WoS Importer:2021-03-19

Semiautomatic segmentation of the kidney in magnetic resonance images using unimodal thresholding - Sandmair, Martin; Hammon, Matthias; Seuss, Hannes; Theis, Ragnar; Uder, Michael; Janka, Rolf Matthias (BMC Research Notes, 2016)
Total kidney volume (TKV) is an important marker for the presence or progression of chronic kidney disease, however, routine ultrasonography underestimates renal volume to a high and varying degree.The aim of this work was to adapt and evaluate a semi-automatic unimodal thresholding method for volumetric analysis of the kidney in native T2-weighted magnetic resonance (MR) images.In a group of healthy volunteers (n = 24; 48 kidneys), we defined a region of interest (ROI) by manually tracing the outline of the kidney in every MR image. An automatic unimodal thresholding algorithm with visual feedback was applied to the probability distribution function of voxel intensities in the ROI to remove intrarenal non-parenchyma volume. For comparison, reference volumes were created by manual segmentation. Intra- and inter-observer reliability was evaluated.There was a small, significant mean difference of 1.5 ml between semi-automatically and manually segmented TKV (p = 0.009, 95% CI [0.4, 2.7]). While intra-observer reliability was good (mean difference 2.9 ml, p < 0.01, 95% CI [1.5, 4.2]) there was a small but significant mean difference of 4.8 ml (p < 0.01, 95% CI [3.6, 5.9]) between the TKV results of different observers. Reference volume correlations were excellent (r = 0.97-0.98). Semi-automated segmentation was significantly faster than manual segmentation; mean difference = 234 s [91-483 s]; p < 0.05. Automatic unimodal thresholding removed a considerable mean volume of 18.7 ml (13.1%) from the coarse manual pre-segmentations.Unimodal thresholding of native MR images is a robust and sufficiently reliable method for kidney segmentation and volumetric analysis. The manual pre-segmentation can be done by non-experts with little introduction.
EVALuna2:14594

Simultaneous Multislice Echo Planar Imaging for Accelerated Diffusion-Weighted Imaging of Malignant and Benign Breast Lesions - Ohlmeyer, Sabine; Palm, Theresa; Janka, Rolf Matthias; Weiland, Elisabeth; Uder, Michael; Wenkel, Evelyn; Laun, Frederik Bernd (Investigative Radiology, 2019)
Objectives Comparison of the diagnostic value of simultaneous multislice (SMS) accelerated diffusion-weighted echo planar imaging (EPI) of malignant and benign lesions of the breast compared with a reference EPI sequence. Materials and Methods The study was approved by the institutional ethics committee. Sixty-eight patients were examined with a diffusion-weighted EPI (reference EPI; TE = 54 milliseconds; TR = 9000 milliseconds; TA, 3:27 minutes) and a diffusion-weighted SMS accelerated EPI (SMS EPI; acceleration factor 2; TE = 58 milliseconds; TR = 4300 milliseconds; TA, 1:53 minutes) in addition to the standard magnetic resonance imaging (MRI) protocol. Further acquisition parameters were as follows: 3 T MAGNETOM Skyra (Siemens Healthcare, Erlangen, Germany), 2.5-mm isotropic resolution, field of view = 185 to 190 × 350 mm2, 62 slices, b = 50 and 800 s/mm2 with 1 and 4 averages, respectively. A dedicated 16-channel bilateral breast coil was used for imaging. Image quality was evaluated with respect to the presence of artifacts, signal voids, and quality of fat suppression. These parameters were rated using a 5-point Likert scale (1 = very strong to 5 = negligible). The apparent diffusion coefficient (ADC) was measured in 72 focal lesions (46 breast carcinomas and 26 benign lesions), and the diagnostic value of the 2 datasets was statistically evaluated and compared. The evaluation was performed a second time excluding cysts. Results Artifacts and signal voids were negligible in both sequences (mean on Likert scale for reference EPI 4.68 vs SMS EPI 4.65, P = 0.52, and mean on Likert scale for reference EPI 4.85 vs SMS EPI 4.77, P = 0.14). Fat suppression was significantly better in SMS EPI (mean on Likert scale 3.28 vs 2.97, P < 0.001, Pearson r = 0.49). For benign lesions, the mean ADC in both EPI sequences was 1.86 · 10-3 mm2/s. For malignant lesions, a mean ADC of 0.90 · 10-3 mm2/s for the reference EPI and 0.89 · 10-3 mm2/s for the SMS EPI was found. No significant difference between the EPI sequences was observed for ADC values (P = 0.75) and for the area under the curve (SMS, 0.985; no SMS, 0.975). The cutoff for differentiation of benign and malignant lesions was at ADC = 1.42 · 10-3 mm2/s for SMS EPI (sensitivity, 1; specificity, 0.88) and at 1.23 · 10-3 mm2/s for the reference EPI (sensitivity, 1; specificity, 0.92). Excluding the cysts, the cutoff for differentiation of benign and malignant lesions was at ADC = 1.11 · 10-3 mm2/s for SMS EPI (sensitivity, 0.89; specificity, 0.93) and at 1.23 · 10-3 mm2/s for the reference EPI (sensitivity, 1; specificity, 0.87). Conclusions Our data indicate that SMS acceleration can be used for diffusion imaging in breast MRI in clinical practice. Simultaneous multislice EPI achieved the same diagnostic accuracy in breast MRI, but in a substantially reduced scan time.
CRIS-Team Scopus Importer:2019-07-26
Keywords: breast; diffusion; DW MRI; DWI; EPI; lesions; simultaneous multislice acceleration; SMS

Simultaneous Segmentation and Registration for FAIR Perfusion Imaging - Siegl, Christian; Martschinke, Jana; Janka, Rolf Matthias; Grosso, Roberto (Bildverarbeitung für die Medizin 2014, 2014)
Renal perfusion might be the key factor in controlling the systemic blood pressure. While up to no now, there is no way to measure renal perfusion non-invasively, a promising technique might be MRimaging with arterial spin labeling. This technique was developed to measure brain perfusion. In contrast to the brain the kidney is moving due to breathing, which makes post processing of the acquired images a demanding issue. In this work, we present a tool that supports a physician in performing kidney perfusion analysis using this technique. To accommodate this, we will show a custom tailored segmentation and registration approach that can cope with the challenges of this technique. By using this tool, the physician can analyze kidney perfusion using less images which enhances usability in clinical day to day applicatio
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD9.simult

Skin Sodium Concentration Correlates with Left Ventricular Hypertrophy in CKD - Schneider, Markus P.; Raff, Ulrike; Kopp, Christoph; Scheppach, Johannes B.; Toncar, Sebastian; Wanner, Christoph; Schlieper, Georg; Saritas, Turgay; Floege, Juergen; Schmid, Matthias; Birukov, Anna; Dahlmann, Anke; et al. (Journal of the American Society of Nephrology, 2017)
The pathogenesis of left ventricular hypertrophy in patients with CKD is incompletely understood. Sodium intake, which is usually assessed by measuring urinary sodium excretion, has been inconsistently linked with left ventricular hypertrophy. However, tissues such as skin and muscle may store sodium. Using (23)sodium-magnetic resonance imaging, a technique recently developed for the assessment of tissue sodium content in humans, we determined skin sodium content at the level of the calf in 99 patients with mild to moderate CKD (42 women; median [range] age, 65 [23-78] years). We also assessed total body overhydration (bioimpedance spectroscopy), 24-hour BP, and left ventricular mass (cardiac magnetic resonance imaging). Skin sodium content, but not total body overhydration, correlated with systolic BP (r=0.33, P=0.002). Moreover, skin sodium content correlated more strongly than total body overhydration did with left ventricular mass (r=0.56, P<0.001 versus r=0.35, P<0.001; P<0.01 between the two correlations). Linear regression analysis demonstrated that skin sodium content is a strong explanatory variable for left ventricular mass, unaffected by BP and total body overhydration. In conclusion, we found skin sodium content to be closely linked to left ventricular mass in patients with CKD. Interventions that reduce skin sodium content might improve cardiovascular outcomes in these patients.
EVALuna2:3863

Skully - An Educational Web Application for the Human Skull - Bertelshofer, Franziska; Brehm, Oliver; Fitzner, Paul; Lammert, Jacqueline; Janka, Rolf Matthias; Paulsen, Friedrich; Greiner, Günther (Bildverarbeitung für die Medizin 2016, 2016)
One fundamental topic in anatomy is the structure of the human skull. Common sources for studying are books, atlases and other two dimensional material which makes it hard to optimally locate the separate parts of the human skull in three dimensional space and understand the relations between them. We developed a browser application visualizing three dimensional models of the human skull. The user can interact with those models, e.g. move them freely to gain insight in the three dimensional structure and position of the single bones, highlight separate bones or groups of them and view textual annotations. In a developer mode those annotations can be edited easily by anatomy experts or course tutors to contain all relevant information. Furthermore the application is platform independent, it can used on e.g. computers with different operating systems, tablets and mobile phones.

Statement of the German Roentgen Society, German Society of Neuroradiology, and Society of German-speaking Pediatric Radiologists on Requirements for the Performance and Reporting of MR Imaging Examinations Outside of Radiology - Hunold, Peter; Bucher, Andreas Michael; Sandstede, Joern; Janka, Rolf Matthias; Fritz, Lars Benjamin; Regier, Marc; Loose, Reinhard; Barkhausen, Joerg; Mentzel, Hans-Joachim; Zimmer, Claus; Antoch, Gerald; Schoenberg, Stefan O.; et al. (Röfo: Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2021)
Background Magnetic Resonance Imaging (MRI) is a very innovative, but at the same time complex and technically demanding diagnostic method in radiology. It plays an increasing role in high-quality and efficient patient management. Quality assurance in MRI is of utmost importance to avoid patient risks due to errors before and during the examination and when reporting the results. Therefore, MRI requires higher physician qualification and expertise than any other diagnostic imaging technique in medicine. This holds true for indication, performance of the examination itself, and in particular for image evaluation and writing of the report. In Germany, the radiologist is the only specialist who is systematically educated in all aspects of MRI during medical specialty training and who must document a specified, high number of examinations during this training. However, also non- radiologist physicians are increasingly endeavoring to conduct and bill MRI examinations on their own.
CRIS-Team WoS Importer:2021-05-21

Stereotactic vacuum-assisted breast biopsy (VABB)–a patients' survey - Eller, Achim; Janka, Rolf Matthias; Lux, Michael P.; Saake, Marc; Schulz-Wendtland, Rüdiger; Uder, Michael; Wenkel, Evelyn (Anticancer Research, 2014)
To analyze how patients experience Stereotactic guided vacuum-assisted breast biopsy (VABB) both physically and mentally.Two hundred and eleven consecutive women underwent VABB using one of two different biopsy devices (ATEC® and Mammotome®). Patients were queried using a questionnaire.One hundred and eighty-nine patients were included. 90% would again prefer VABB over a surgical biopsy. Average grading for the condition during the procedure was 2.5 (very good to good) and 2.1 (very good) for the condition the week following VABB. Minor complications were mentioned in 37%. (>90% pain and hematoma). 97% of the women were satisfied by the cosmetic results. Patients with malignant histology and younger age experienced the procedure significantly worse. A significant higher rate of minor complications was found in younger patients and in the ATEC® group.VABB is a physical and mental stressor to the women. Nonetheless, the majority of women indeed prefer the VABB.
EVALuna2:14365

Stress examination of flexor tendon pulley rupture in the crimp grip position: a 1.5-Tesla MRI cadaver study - Bayer, Thomas; Fries, Simon; Schweizer, Andreas; Schoeffl, Isabelle; Janka, Rolf Matthias; Bongartz, Georg (Skeletal Radiology, 2015)
The objectives of this study were the evaluation of flexor tendon pulley rupture of the fingers in the crimp grip position using magnetic resonance imaging (MRI) and the comparison of the results with MRI in the neutral position in a cadaver study.MRI in the crimp grip position and in the neutral position was performed in 21 cadaver fingers with artificially created flexor tendon pulley tears (combined pulley rupture, n = 14; single pulley rupture, n = 7). Measurement of the distance between the tendon and bone was performed. Images were evaluated by two readers, first independently and in cases of discrepancy in consensus. Sensitivity and specificity for detecting combined pulley ruptures were calculated.Tendon bone distances were significantly higher in the crimp grip position than in the neutral position. Sensitivity and specificity for detecting combined pulley rupture were 92.86 % and 100 % respectively in the crimp grip position and 78.57 % and 85.71 % respectively in the neutral position. Kappa values for interobserver reliability were 0.87 in the crimp grip position and 0.59 in the neutral position.MRI examination in the crimp grip position results in higher tendon bone distances by subjecting the pulleys to a higher strain, which facilitates image evaluation with higher interobserver reliability, higher sensitivity, and higher specificity for combined pulley rupture compared with examination in the neutral position.
EVALuna2:14345

Stress fractures - Current recommendations and principles for diagnosis and therapy Problemdiagnose Stressfraktur – Aktuelle Empfehlungen und Prinzipien zur Diagnostik und Therapie - Heiß, Rafael; Lutter, Christoph; Kastner, Tom; Janka, Rolf Matthias; Uder, Michael; Hotfiel, Thilo (Sport-Orthopädie, Sport-Traumatologie, 2022)
Stress fractures and stress reactions are among the injuries caused by overuse (“overuse injuries”) and can result in significant training and competition failures for affected athletes. Repetitive load effects that exceed the ability to cope with stress and adaptability, combined with intrinsic and extrinsic risk factors or tactical training errors, are considered to be the main cause of stress fractures. These and possible accompanying individual risk profiles are diverse and require complex and often interdisciplinary care. The majority of stress fractures heal easily and the recovery of full performance and resilience is usually given. However, if the diagnosis is delayed or inadequate (some injury entities require consistent decision-making regarding surgical therapy) or if secondary risk factors are not taken into account, prolonged healing processes, recurrent injuries or even multiple injury locations can occur at the same time. An early diagnosis and the beginning of a stage-appropriate therapy, including the consideration of existing risk factors, are therefore of essential importance.
CRIS-Team Scopus Importer:2022-03-11
Keywords: Marching fracture; MRI; Running injury; Stress fracture; Stress reaction; X-ray

Structured image diagnosis of vertebral body degeneration and disc damage - Binary image criteria and comparison for systematic image analysis in occupational diseases 2108/2110. - Braunschweig, Rainer; Kildal, Daniela; Meyer-Clement, Michael; Janka, Rolf Matthias; Tiemann, Andreas (Röfo: Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2024)
BACKGROUND: Occupationally related limitations of earning capacity can be recognized under social legislation and may be subject to compensation ("reduction in earning capacity"). For this purpose, legislators have defined a list of occupational diseases ("BK list"). Recognition of an occupational disease requires a legal assessment procedure based on a medical appraisal. The aim of the assessment is to prove the "causality" and the "causality giving rise to liability". METHOD: In addition to clinical findings and workplace analyses, imaging methods (projection radiography, MRI) are primarily used to substantiate liability. These methods enable proof of load-conforming damage patterns for occupational diseases 2108/2110 (damage to intervertebral discs). RESULTS AND CONCLUSION: In addition to the legal background, the following review article primarily presents the image criteria for load-conforming damage patterns of the spine. On the basis of the consensus paper on the "Assessment of occupational disc diseases of the lumbar spine", image criteria are assigned to age-atypical grades of findings, and "typical constellations of findings" are defined for vibration (BK 2108) or lifting (BK 2110) loads. The aim of Part 1 is to explain the image criteria of the comparative images presented as image plates in Part 2 and thus to present a reference catalog of findings. KEY STATEMENTS: · Occupational diseases are defined by legislators in the "List of Occupational Diseases".. · For occupational intervertebral disc diseases (BK 2108/2110), constellations of findings are defined.. · In the context of imaging diagnostics, a large number of image criteria are used.. · Part 1 explains the basics.. · Part 2 provides the image criteria on the basis of "comparative images" as a reference catalog.. CITATION FORMAT: · Braunschweig R, Kildal D, Meyer-Clement M et al. Structured image diagnosis of vertebral body degeneration and disc damage - Binary image criteria and comparison for systematic image analysis in occupational diseases 2108/2110. Fortschr Röntgenstr 2024; 196: 347 - 353.
EVALuna2:557959
Keywords: occupational diseases; degenerative spine conditions; structured image diagnosis; intervertebral disc degeneration; systematic medical image analysis

Structured image diagnosis of vertebral body degeneration and intervertebral disc damage - Binary image criteria and comparison for systematic image analysis for occupational diseases 2108 and 2110. Part 2: “Comparison images” - Braunschweig, Rainer; Kildal, Daniela; Meyer-Clement, Michael; Tiemann, Andreas; Janka, Rolf Matthias (Röfo: Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2024)
BACKGROUND: Job-related limitations of earning capacity are eligible for recognition under social legislation and may be subject to compensation (see Part 1). METHOD: For the recognition of an occupational disease (BK), diagnostic imaging is required as part of the legal determination procedure for occupational diseases 2108/2110 ("occupational disc disease"). The focus is on image criteria on X-ray images and MRI examinations. In a consensus paper under the guidance of the German Social Accident Insurance Institutions from 2005, the characteristic patterns are defined and explained extensively and summarized in typical occupation-related constellations. This article presents representative image examples as a reference system for expert reporting as far as the typical patterns from the consensus paper are concerned. CONCLUSION: In Part 2, comparison images with the typical findings of the vertebral bodies and intervertebral discs according to occupational diseases are systematically presented, explained, and offered as a reference system for expert assessment. The image criteria can be used as "evidence by eye" (Heuck) in the recognition procedure. KEY POINTS: · Occupational diseases are defined by the legislator in the "List of Occupational Diseases".. · For occupational intervertebral disc diseases (OD nos. 2108/2110), constellations of findings are defined.. · Within the scope of diagnostic imaging, a large number of image criteria are used.. · Part 1 explains the basics and the legal background.. · Part 2 provides the image criteria on the basis of "comparison images" as a reference catalog.. CITATION FORMAT: · Braunschweig R, Kildal D, Meyer-Clement M et al. Structured image diagnosis of vertebral body degeneration and intervertebral disc damage - Binary image criteria and comparison for systematic image analysis for occupational diseases 2108 and 2110. Fortschr Röntgenstr 2024; 196: 912 - 920.
EVALuna2:568212

T2 Mapping as a New Method for Quantitative Assessment of Cartilage Damage in RA - Renner, Nina; Kleyer, Arnd; Krönke, Gerhard; Simon, David; Söllner, Stefan; Rech, Jürgen; Uder, Michael; Janka, Rolf Matthias; Schett, Georg; Welsch, Goetz; Pachowsky, Milena (Journal of Rheumatology, 2019)
OBJECTIVE: Rheumatoid arthritis (RA) is associated with damage of the articular cartilage and the periarticular bone. While imaging of bone damage has substantially improved in the last years, direct imaging of the articular cartilage of the hand joints in patients with RA is still challenging. METHODS: 3 Tesla Magnetic Resonance Imaging (MRI) was done in 30 RA patients and T2 relaxation times visualizing alteration in the collagen network and hydration of articular cartilage were mapped in six cartilage regions of the metacarpophalangeal joints 2 and 3. Values were related to autoantibody (anti-citrullinated peptide antibodies (ACPA), rheumatoid factor (RF)) status, disease duration, disease activity as well as sex and age of the RA patients. RESULTS: T2 relaxation times could be reliably measured in the six regions of the metacarpophalangeal joints. Significantly higher relaxation times indicating more advanced cartilage alterations were observed in ACPA-positive (p=0.001-0.010) and RF-positive patients (p=0.013-0.025) as well as those with longer disease duration (>3 years; p=0.028-0.043). Current disease activity, sex and age did not influence T2 relaxation times. CONCLUSION: These data show that cartilage damage can be localized and quantified in the hand joints of RA patients by T2 mapping. Furthermore, ACPA and RF positivity as well as disease duration appear to be the crucial factors influencing cartilage damage.
EVALuna2:210913

The effect of sacubitril/valsartan compared to olmesartan on cardiovascular remodelling in subjects with essential hypertension: the results of a randomized, double-blind, active-controlled study - Schmieder, Roland; Wagner, Frank; Mayr, Michael; Delles, Christian; Ott, Christian; Keicher, Christian; Hrabak-Paar, Maja; Heye, Tobias; Aichner, Solveig; Khder, Yasser; Yates, Denise; Albrecht, Diego; et al. (European Heart Journal, 2017)
Progressive aortic stiffening eventually leads to left ventricular (LV) hypertrophy and heart failure if left untreated. Anti-hypertensive agents have been shown to reverse this to some extent. The effects of sacubitril/valsartan (LCZ696), a dual-action angiotensin receptor blocker (ARB), and neprilysin inhibitor, on arterial stiffness and LV remodelling have not been investigated.This was a randomized, multi-centre, double-blind, double-dummy, active-controlled, parallel group, study to compare the effects on cardiovascular remodelling of sacubitril/valsartan with those of olmesartan in patients with hypertension and elevated pulse pressure. Magnetic resonance imaging scans were used to assess LV mass and local aortic distensibility, at baseline and at 12 and 52 weeks after initiation of treatment. Central pulse and systolic pressure were determined using a SphymoCor® XCEL device at each time point. A total of 114 patients were included, with 57 in each treatment group. The mean age was 59.8 years, and 67.5% were male. Demographic characteristics did not vary between the two sets of patients. Left ventricular mass index decreased to a greater extent in the sacubitril/valsartan group compared to the olmesartan group from baseline to 12 weeks (-6.36 vs. -2.32 g/m2; P = 0.039) and from baseline to 52 weeks (-6.83 vs. -3.55 g/m2; P = 0.029). These differences remained significant after adjustment for systolic blood pressure (SBP) at follow-up (P = 0.036 and 0.019 at 12 and 52 weeks, respectively) and similar signals (though formally non-significant) were observed after adjusting for changes in SBP (P = 0.0612 and P = 0.0529, respectively). There were no significant differences in local distensibility changes from baseline to 12 or 52 weeks between the two groups; however, there was a larger reduction in central pulse pressure for the sacubitril/valsartan group compared to the olmesartan group (P = 0.010).Since LV mass change correlates with cardiovascular prognosis, the greater reductions in LV mass indicate valuable advantages of sacubitril/valsartan compared to olmesartan. The finding that LV mass index decrease might be to some extent independent of SBP suggests that the effect of the dual-acting agent may go beyond those due to its BP-lowering ability.
EVALuna2:3950

Third-generation dual-source 70-kVp chest CT angiography with advanced iterative reconstruction in young children: image quality and radiation dose reduction - Rompel, Oliver; Glöckler, Martin; Janka, Rolf Matthias; Dittrich, Sven; Cesnjevar, Robert; Lell, Michael; Uder, Michael; Hammon, Matthias (Pediatric Radiology, 2016)
Many technical updates have been made in multi-detector CT.To evaluate image quality and radiation dose of high-pitch second- and third-generation dual-source chest CT angiography and to assess the effects of different levels of advanced modeled iterative reconstruction (ADMIRE) in newborns and children.Chest CT angiography (70 kVp) was performed in 42 children (age 158 ± 267 days, range 1-1,194 days). We evaluated subjective and objective image quality, and radiation dose with filtered back projection (FBP) and different strength levels of ADMIRE. For comparison were 42 matched controls examined with a second-generation 128-slice dual-source CT-scanner (80 kVp).ADMIRE demonstrated improved objective and subjective image quality (P < .01). Mean signal/noise, contrast/noise and subjective image quality were 11.9, 10.0 and 1.9, respectively, for the 80 kVp mode and 11.2, 10.0 and 1.9 for the 70 kVp mode. With ADMIRE, the corresponding values for the 70 kVp mode were 13.7, 12.1 and 1.4 at strength level 2 and 17.6, 15.6 and 1.2 at strength level 4. Mean CTDIvol, DLP and effective dose were significantly lower with the 70-kVp mode (0.31 mGy, 5.33 mGy*cm, 0.36 mSv) compared to the 80-kVp mode (0.46 mGy, 9.17 mGy*cm, 0.62 mSv; P < .01).The third-generation dual-source CT at 70 kVp provided good objective and subjective image quality at lower radiation exposure. ADMIRE improved objective and subjective image quality.
EVALuna2:14476

Twelve-year survival and immune correlates in dendritic cell-vaccinated melanoma patients - Gross, Stefanie; Erdmann, Michael; Haendle, Ina; Voland, Steve; Berger, Thomas; Schultz, Erwin; Strasser, Erwin; Dankerl, Peter; Janka, Rolf Matthias; Schliep, Stefan; Heinzerling, Lucie; Sotlar, Karl; et al. (JCI Insight, 2017)
BACKGROUND: Reports on long-term (≥10 years) effects of cancer vaccines are missing. Therefore, in 2002, we initiated a phase I/II trial in cutaneous melanoma patients to further explore the immunogenicity of our DC vaccine and to establish its long-term toxicity and clinical benefit after a planned 10-year followup. METHODS: Monocyte-derived DCs matured by TNFα, IL-1β, IL-6, and PGE2 and then loaded with 4 HLA class I and 6 class II-restricted tumor peptides were injected intradermally in high doses over 2 years. We performed serial immunomonitoring in all 53 evaluable patients. RESULTS: Vaccine-specific immune responses including high-affinity, IFNγ-producing CD4+ and lytic polyfunctional CD8+ T cells were de novo induced or boosted in most patients. Exposure of mature DCs to trimeric soluble CD40 ligand, unexpectedly, did not further enhance such immune responses, while keyhole limpet hemocyanin (KLH) pulsing to provide unspecific CD4+ help promoted CD8+ T cell responses - notably, their longevity. An unexpected 19% of nonresectable metastatic melanoma patients are still alive after 11 years, a survival rate similar to that observed in ipilimumab-treated patients and achieved without any major (>grade 2) toxicity. Survival correlated significantly with the development of intense vaccine injection site reactions, and with blood eosinophilia after the first series of vaccinations, suggesting that prolonged survival was a consequence of DC vaccination. CONCLUSIONS: Long-term survival in advanced melanoma patients undergoing DC vaccination is similar to ipilimumab-treated patients and occurs upon induction of tumor-specific T cells, blood eosinophilia, and strong vaccine injection site reactions occurring after the initial vaccinations. TRIAL REGISTRATION: ClinicalTrials.gov NCT00053391. FUNDING: European Community, Sixth Framework Programme (Cancerimmunotherapy LSHC-CT-2006-518234; DC-THERA LSHB-CT-2004-512074), and German Research Foundation (CRC 643, C1, Z2).
EVALuna2:14632

Ultra-High b-Value Diffusion-Weighted Imaging-Based Abbreviated Protocols for Breast Cancer Detection - Ohlmeyer, Sabine; Laun, Frederik Bernd; Bickelhaupt, Sebastian; Palm, Theresa; Janka, Rolf Matthias; Weiland, Elisabeth; Uder, Michael; Wenkel, Evelyn (Investigative Radiology, 2021)
Objectives Contrast-enhanced (CE) magnetic resonance imaging (MRI) is the most effective imaging modality for breast cancer detection. A contrast agent-free examination technique would be desirable for breast MRI screening. The purpose of this study was to evaluate the capability to detect and characterize suspicious breast lesions with an abbreviated, non-contrast-enhanced MRI protocol featuring ultra-high b-value diffusion-weighted imaging (DWI) compared with CE images. Materials and Methods The institutional review board-approved prospective study included 127 female subjects with different clinical indications for breast MRI. Magnetic resonance imaging examinations included DWI sequences with b-values of 1500 s/mm(2) (b1500) and 2500 s/mm(2) (b2500), native T1- and T2-weighted images, and CE sequences at 1.5 T and 3 T scanners. Two reading rounds were performed, including either the b1500 or the b2500 DWI in consecutive assessment steps: (A) maximum intensity projections (MIPs) of DWI, (B) DWI and apparent diffusion coefficient maps, (C) as (B) but with additional native T1- and T2-weighted images, and (D) as (C) but with additional CE images (full-length protocol). Two readers independently determined the presence of a suspicious lesion. Histological confirmation was obtained for conspicuous lesions, whereas the full MRI data set was obtained for inconspicuous and clearly benign lesions. Statistical analysis included calculation of diagnostic accuracy and interrater agreement via the intraclass correlation coefficient. Results The cohort comprised 116 cases with BI-RADS 1 findings and 138 cases with BI-RADS >= 2 findings, including 38 histologically confirmed malignancies. For (A), breasts without pathological findings could be recognized with high diagnostic accuracy (negative predictive value, >= 97.0%; sensitivity, >= 92.1% for both readers), but with a limited specificity (>= 58.3%; positive predictive value, >= 28.6%). Within the native readings, approach (C) with b2500 performed best (negative predictive value, 99.5%; sensitivity, 97.4%; specificity, 88.4%). The intraclass correlation coefficient was between 0.683 (MIP b1500) and 0.996 (full protocol). Conclusions A native abbreviated breast MRI protocol with advanced high b-value DWI might allow nearly equivalent diagnostic accuracy as CE breast MRI and seems to be well suited for lesion detection purposes.
CRIS-Team WoS Importer:2021-10-01

Update cartilage imaging of the small joints: Focus on high-field MRI [Update Knorpelbildgebung der kleinen Gelenke: Fokus Hochfeld-MRT] - Heiß, Rafael; Janka, Rolf Matthias; Uder, Michael; Nagel, Armin Michael; Trattnig, S.; Roemer, Frank (Radiologe, 2019)
Background: Cartilage imaging of small joints is increasingly of interest, as early detection of cartilage damage may be relevant regarding individualized surgical therapies and long-term outcomes. Purpose: The aim of this review is to explain modern cartilage imaging of small joints with emphasis on MRI and to discuss the role of methods such as CT arthrography as well as compositional and high-field MRI. Materials and methods: A PubMed literature search was performed for the years 2008–2018. Results: Clinically relevant cartilage imaging to detect chondral damage in small joints remains challenging. Conventional MRI at 3 T can still be considered as a reference for cartilage imaging in clinical routine. In terms of sensitivity, MR arthrography (MR-A) and computed tomography arthrography (CT-A) are superior to non-arthrographic MRI at 1.5 T in the detection of chondral damage. Advanced degenerative changes of the fingers and toes are usually sufficiently characterized by conventional radiography. MRI at field strengths of 3 T and ultrahigh-field imaging at 7 T can provide additional quantifiable, functional and metabolic information. Conclusion: Standardized cartilage imaging plays an important role in clinical diagnostics in the ankle joint due to the availability of different and individualized therapeutic concepts. In contrast, cartilage imaging of other small joints as commonly performed in clinical studies has not yet become standard of care in daily clinical routine. Although individual study results are promising, additional studies with large patient collectives are needed to validate these techniques. With rapid development of new treatment concepts radiological diagnostics will play a more significant role in the diagnosis of cartilage lesions of small joints.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Ankle; Glycosaminoglycans; Literature review; Magnetic resonance imaging; Wrist

Update: Posttreatment Imaging of the Knee after Cartilage Repair. - Heiß, Rafael; Guermazi, Ali; Janka, Rolf Matthias; Uder, Michael; Li, Xinning; Hayashi, Daichi; Roemer, Frank (Seminars in Musculoskeletal Radiology, 2022)
Focal cartilage lesions are common pathologies at the knee joint that are considered important risk factors for the premature development of osteoarthritis. A wide range of surgical options, including but not limited to marrow stimulation, osteochondral auto- and allografting, and autologous chondrocyte implantation, allows for targeted treatment of focal cartilage defects. Arthroscopy is the standard of reference for the assessment of cartilage integrity and quality before and after repair. However, deep cartilage layers, intrachondral composition, and the subchondral bone are only partially or not at all visualized with arthroscopy. In contrast, magnetic resonance imaging offers noninvasive evaluation of the cartilage repair site, the subchondral bone, and the soft tissues of the joint pre- and postsurgery. Radiologists need to be familiar with the different surgical procedures available and their characteristic postsurgical imaging appearances to assess treatment success and possible complications adequately. We provide an overview of the most commonly performed surgical procedures for cartilage repair at the knee and typical postsurgical imaging characteristics.
EVALuna2:506329

Using Cartilage MRI T2-Mapping to Analyze Early Cartilage Degeneration in the Knee Joint of Young Professional Soccer Players - Waldenmeier, Leonie; Evers, Christoph; Uder, Michael; Janka, Rolf Matthias; Hennig, Friedrich; Pachowsky, Milena; Welsch, Götz Hannes (Cartilage, 2019)
Objective: To evaluate and characterize the appearance of articular cartilage in the tibiofemoral joint of young professional soccer players using T2-relaxation time evaluation on magnetic resonance imaging (MRI). Design: In this study, we included 57 male adolescents from the youth academy of a professional soccer team. The MRI scans were acquired of the knee joint of the supporting leg. An “early unloading” (minute 0) and “late unloading” (minute 28) T2-sequence was included in the set of images. Quantitative T2-analysis was performed in the femorotibial joint cartilage in 4 slices with each 10 regions of interest (ROIs). Statistical evaluation, using Wilcoxon signed-rank tests, was primarily performed to compare the T2 values of the “early unloading” and “late unloading.” Results: When comparing “early unloading” with “late unloading,” our findings showed a significant increase of T2-relaxation times in the weightbearing femoral cartilage of the medial (P < 0.001) and lateral (P < 0.001) compartment of the knee and in the tibial cartilage of the medial compartment (P < 0.001). Conclusion: In this study, alterations of the cartilage were found with a maximum in the medial condyle where the biomechanical load of the knee joint is highest, as well as where most of the chronic cartilage lesions occur. To avoid chronic damage, special focus should be laid on this region.
CRIS-Team Scopus Importer:2019-07-02
Keywords: articular cartilage; biomechanics; knee; magnetic resonance imaging; sports injury

Vascular and renal hemodynamic changes after renal denervation - Ott, Christian; Janka, Rolf Matthias; Schmid, Axel; Titze, Stephanie; Ditting, Tilmann; Sobotka, Paul A.; Veelken, Roland; Uder, Michael; Schmieder, Roland (Clinical Journal of the American Society of Nephrology, 2013)
Background and objectives Renal denervation (RDN) has been shown to be effective in reducing BP in treatmentresistant hypertension. Measurement of the renal and sympathetic activity revealed a decrease in sympathetic drive to the kidney and small resistance vessels after RDN. However, the consequences on renal perfusion and renal vascular resistance (RVR), as well as central hemodynamics, are unknown. Design, setting, participants, & measurements Nineteen patients with treatment-resistant hypertension (office BP140/90mmHg, despite at least three antihypertensive drugs [including a diuretic], and diagnosis confirmed by 24-hour ambulatory BPmonitoring) underwent RDNbetween January andOctober 2011. Renal perfusion and RVR were noninvasively assessed by magnetic resonance imaging with arterial spin labeling, and renal function was assessed by estimating GFR before (day 21), after (day +1), and again after 3 months of RDN. Central hemodynamics was assessed using pulse wave analysis at day 21 and after 6 months of RDN. Results Peripheral office BP (systolic, 158±26 versus 142±23mmHg, P=0.002; diastolic, 83±13 versus 76±9mmHg, P=0.02) and mean systolic 24-hour ambulatory BP (159±17 versus 152±17 mmHg, P=0.02) were significantly reduced 6 months after RDN. Renal perfusion was not statistically different between day 21 and day +1 (256.8 [interquartile range (IQR), 241-278] versus 263.4 [IQR, 252-277] ml/min per 100 g; P=0.17) as well as after 3 months (256.8 [IQR, 241-278] versus 261.2 [IQR, 240-285] ml/min per 100 g; P=0.27) after RDN. RVR dropped (432.1 [IQR, 359-525] versus 390.6 [IQR, 338-461] AU; P=0.02), whereas renal function was not statistically different at any time point. Central systolic BP (145±31 versus 131628 mmHg; P=0.009), diastolic BP (85±18 versus 80±14 mmHg; P=0.03), and central pulse pressure (61±18 versus 52±18 mmHg; P=0.02) were significantly reduced 6 months after RDN. Central augmentation index (24±8 versus 20±8%; P=0.02) was decreased 6 months after RDN. Conclusion The data indicate that RDN significantly reduced peripheral and central BP. Despite reduced systemic BP, renal perfusion and function did not change after RDN. © 2013 by the American Society of Nephrology.
CRIS-Team Scopus Importer:2023-03-08

Vertebral body fractures of unknown origin in cancer patients receiving MDCT: reporting by radiologists and awareness by clinicians - Wild, Melanie; Dankerl, Peter; Hammon, Matthias; Uder, Michael; Janka, Rolf Matthias (SpringerPlus, 2016)
To evaluate prevalence, radiological reporting and clinical management of pathologic vertebral body fractures (VBFs) of unknown origin in cancer patients receiving computed tomography (CT) examinations.We investigated all CT examinations (over 1 year) of male and female patients with an underlying malignancy and an increased risk of osteoporosis (age 55-79 years) for the presence of VBFs. We evaluated midline sagittal CT-reformations of the spine for prevalence, fracture type, severity and location, the accuracy and style of radiological reporting, subsequent clinical management and documentation in hospital discharge letters.848 patients were investigated. We found 143 VBFs in 94 (11 %) patients. 6, 49, and 45 % were grade 1, grade 2, and grade 3 fractures, respectively, while 20, 66, and 14 % were wedge, biconcave and crush fractures, respectively. 32 (34 %) radiological reports correctly classified VBFs as fractures, 25 (27 %) reports recognized VBFs, but did not type them, and VBFs were not described in 37 (39 %) reports. In 3 (3 %) patients further clinical work-up of VBFs was performed, while only 8 (9 %) hospital discharge letters contained the information of the presence of pathologic VBFs of unknown origin.VBFs of unknown origin appear frequently in cancer patients, however, clinical management and documentation was found in only few cases. Moreover, especially in cancer patients consistent radiological reporting of VBFs seems important, as aetiology of VBFs could be from osteoporosis, disease progression or oncological therapy, however, reporting is still performed inconsistently.
EVALuna2:14589

Virtual Computed Tomography Colonography: Evaluation of 2D and Virtual 3D Image Quality of Sub-mSv Examinations Enabled by Third-generation Dual Source Scanner Featuring Tin Filtering - Seuß, Hannes; Janka, Rolf Matthias; Hammon, Matthias; Uder, Michael; Dankerl, Peter; Cavallaro, Alexander Josef (Academic Radiology, 2018)
RATIONALE AND OBJECTIVES: To evaluate two- and three-dimensional (2D and 3D) image quality of sub-milliSievert (mSv) computed tomography (CT) colonography utilizing a third-generation dual source CT scanner featuring a tin filter. METHODS: We retrospectively evaluated 26 consecutive patients who underwent third-generation dual source CT colonography, nine with the standard-dose clinical-scan protocol (SDP) and 17 with a low-dose protocol (LDP) featuring a tin filter. Radiation dose was evaluated by volume computed tomography dose index (CTDIvol), dose length product (DLP), effective dose (E), and size-specific dose estimate. Objective image quality was evaluated utilizing signal-to-noise ratio (SNR) derived from standardized placed regions of interest on the transverse 2D images and the ratio of SNR/CTDIvol (normalized SNR). Two radiologists in consensus assessed subjective image quality of the virtual 3D images. RESULTS: There were no significant differences in subjective image quality (P = .661). All examinations were rated "excellent" or "good" for diagnostic confidence. The mean total for DLP/E was 143.4 ± 29.8 mGy/3.00 ± 0.40 mSv in the SDP and therefore significantly higher than in the LDP with 36.9 ± 8.7 mGy/0.75 ± 0.16 mSv (P < .001). The SNR was 8.9 ± 2.1 in the SDP and 4.9 ± 0.8 in the LDP. CONCLUSIONS: Third-generation dual source CT featuring a tin filter enables consistent sub-mSv colonography without substantially impairing image quality.
EVALuna2:34692

YYY BRINGING TOGETHER BODY AND MIND: THE RELATION OF THE PSYCHOLOGICAL AND PHYSIOLOGICAL STRESS RESPONSE TO MRI EXAMINATIONS CONSIDERING FURTHER INFLUENCING FACTORS - Madl, Janika; Janka, Rolf Matthias; Bay, Susanne; Rohleder, Nicolas (PSYCHOSOMATIC MEDICINE, 2021)
CRIS-Team WoS Importer:2021-09-17